Selective CO2 and H-2 adsorption in a chiral magnesium-based metal organic framework (Mg-MOF) with open metal sites - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Journal of Materials Chemistry, 2010)
A rare porous magnesium-based metal-organic framework, Mg-MOF-1 [Mg(3,5-PDC)(H2O)], was synthesized solvothermally in DMF. Structural determination by X-ray single-crystal diffraction technique reveals that this chiral MOF (space group P6(1)22) is constructed by helical assembly of Mg2+ ions with achiral 3,5-pyridine dicarboxylates and coordinating water molecules, to form a three-dimensional framework with parallel hexagonal channels. The structural detail of its 0D analogue Mg-MOF-2 [Mg(2,4-PDC)(H2O)(3)] has been discussed to show how subtle variation in the ligand architecture changes the resulting structure from 0D to 3D. Mg-MOF-1 remains robust and porous upon evacuation of the coordinating water molecules. This is the first report of a chiral hexagonal Mg-MOF synthesized from an achiral organic building unit. Open Mg metal sites show selective hydrogen (H-2) adsorption (ca. 0.8 wt% at 77 K) and carbon dioxide (CO2) uptake (ca. 0.7 mmol g(-1) at 298 K) over nitrogen at 1 atm. Ab initio quantum chemical calculation of adsorption energies and possible adsorption sites of hydrogen molecules are also reported.

Structural diversity in a series of metal-organic frameworks (MOFs) composed of divalent transition metals, 4,4 `-bipyridine and a flexible carboxylic acid - Pachfule, Pradip; Panda, Tamas; Dey, Chandan; Banerjee, Rahul (Crystengcomm, 2010)
A series of flexible metal-organic frameworks (MOFs) have been successfully synthesized under hydrothermal condition using 1,3-adamantanediacetic acid (C(14)H(20)O(4), H(2)ADA) as a flexible dicarboxylate building block, 4,4'-bipyridine and transition metal ions [Cd(II), Zn(II), and Mn(II)] as metal centers in DMF and aqueous media. These MOFs formulated as [Cd(ADA)(4,4'-bipy)(0.5)]center dot(DMF) (Cd-ADA-1), [Mn(ADA)(4,4'-bipy)(0.5)]center dot(DMF) (Mn-ADA-1), Zn(ADA)(4,4'-bipy)(0.5) (Zn-ADA-1), and [Mn(HADA)(2)(4,4'-bipy)(H(2)O)(2)] (Mn-ADA-2) (ADA = 1,3-adamantanediacetate, 4,4'-bipy = 4,4'-bipyridine and DMF = N,N'-dimethyl formamide) display interesting 1D, 2D and 3D structural features depending on the solvent of synthesis. All these MOFs were structurally determined by single-crystal X-ray diffraction. The coordination modes of this ligand are discussed and in addition, thermal stability and hydrogen (H(2)) and carbon-dioxide (CO(2)) adsorption properties of Cd-ADA-1, Mn-ADA-1 and Zn-ADA-1 are also presented. Hydrogen sorption at 77 K and up to 1 atm is found to be 0.42, 0.72 and 1.36 wt% without saturation for Zn-ADA-1, Mn-ADA-1 and Cd-ADA-1 samples.

Structural diversity in partially fluorinated metal organic frameworks (F-MOFs) composed of divalent transition metals, 1,10-phenanthroline, and fluorinated carboxylic acid - Pachfule, Pradip; Dey, Chandan; Panda, Tamas; Vanka, Kumar; Banerjee, Rahul (Crystal Growth & Design, 2010)
Seven new partially fluorinated metal-organic frameworks (F-MOFs) have been synthesized under different solvothermal conditions (H(2)O or N,N-dimethylformamide (DMF)) from transition metal cations [Zn(II), Co(II), and Mn(II)], 1,10-phenanthroline (phen), and 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C(17)H(10)F(6)O(4), H(2)hfbba) to determine the influence of reaction conditions on the formation of metal-organic frameworks. This family of materials displays a striking degree of structural similarity depending on the solvent of synthesis. Of the seven materials, two contain three-dimensional connectivity: Co(3)(hfbba)(6)(phen)(2) (F-MOF-6) and Mn(3)(hfbba)(6)(Phen)(2) (F-MOF-10). Three materials are one-dimensional structures: Zn(hfbba)(0.5)(phen)(HCO(2)) (F-MOF-8), Mn(Hhfbba)(2)(Phen) (F-MOF-11), and [Mn(hfbba)(2)(dm-phen)]center dot(H(2)O) (F-MOF-11A). Lastly, Co(hfbba)(phell)(2)center dot 2(H(2)hfbba)(H(2)O)(HCO(2)) (F-MOF-7) and Zn(hfbba)(phen)(2)center dot 2(H(2)hfbba) (H(2)O)-(HCO(2)) (F-MOF-9) are discrete zero-dimensional molecular complexes. F-MOF-6 and -10, which feature it three-dimensional (3D) framework with pcu topolgy are formed in DMF like F-MOF-8 and at 85 degrees C. The remaining F-MOFs are formed by a solvothermal reaction at 120 degrees C in water. F-MOF-7 and -9 are isostructural discrete zero-dimensional molecular complexes (a similar to 19.5; b similar to 13.7; c similar to 26.2/29.6 angstrom; beta similar to 99.9/120.04; V similar to 6840 angstrom(3)). All these F-MOFs were structurally determined by single-crystal X-ray diffraction. Solid-state properties such its UV-vis and the thermal stability of F-MOF-6 to -11A have also been studied. Insight into the factors influencing the preferred crystallization of a specific complex over others has been obtained from full quantum chemical (QM) calculations using density functional theory (DFT).

Structural, magnetic, and gas adsorption study of a two-dimensional tetrazole-pyrimidine based metal-organic framework - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2010)
A new two-dimensional (2D) metal-organic framework, Cu-TP-1, has been synthesized under solvothermal conditions (DMF) from the transition metal cation Cu(II) and 2-tetrazole pyrimidine (C5H5N6, H-TP). The structure has been determined by single crystal X-ray crystallography which shows a (6,3) honeycomb 2D net with perpendicular one-dimensional channels. Permanent porosity of Cu-TP-1 has been determined by the nitrogen adsorption isotherm. Cu-TP-1 show interesting H-2 and CO2 uptake. CO2 uptake of Cu-TP-1 (at 298 K, 1 atm pressure) is seen to be comparable to the recently reported ZIF-95 which outperforms ZIF-100 and BPL carbon. The magnetic properties show an antiferromagnetically coupled Cu ... Cu interaction down to 8 K with a Weiss temperature around 108 K.

Synthesis and structural comparisons of five new fluorinated metal organic frameworks (F-MOFs) - Pachfule, Pradip; Dey, Chandan; Panda, Tamas; Banerjee, Rahul (Crystengcomm, 2010)
A series of fluorinated metal-organic frameworks (F-MOFs) have been successfully synthesized under hydrothermal condition using 4,40-(hexafluoroisopropylidene) bis(benzoic acid) (C(17)H(10)F(6)O(4), H(2)hfbba) as a flexible dicarboxylate building block, Cu(+2) and various heterocyclic co-ligands. These F-MOFs formulated as [Cu(hfbba)(phen)(2)]center dot 2(H(2)hfbba)(H(2)O)(HCO(2)) (F-MOF-1), [Cu(hfbba)(2)(2,2'-bipy) 2(H(2)O)] (F-MOF-2), [Cu(hfbba)(4,4'-dime-2,2'-bipy)(HCO(2))]center dot(hfbba)(H(2)O) (F-MOF-3), [Cu(2)(hfbba)(2)(3-mepy)(2)]center dot(DMF) 2(3-mepy) (F-MOF-4), and [Cu(hfbba)(2)(phen)(2)]center dot 0.5(DMF) (F-MOF5) (hfbba = 4,4'-(Hexafluoroisopropylidene) bis(benzoate), phen 1,1'-phenanthroline; 2,2'-bipy 2,2'-bipyridine; 4,4'dime-2,2'-bipy 4,4'-dimethyl 2,2'-bipyridine; 3-mepy 3-methyl-pyridine and DMF dimethyl formamide) display interesting H-bonded, 1D and 2D structural features. All these F-MOFs were structurally determined by single-crystal X-ray diffraction. F-MOF-1 and 5 form a distorted octahedral Cu(+2) secondary building unit (SBU). F-MOF-5 forms a one-dimensional architecture constructed from Cu(2+) ions bridged by phen anions and two types of 4 hfbba ligands while in F-MOF-1, two among the three acid co-ligands are not coordinated with Cu(2+) ions. F-MOF-2 displays dinuclear SBUs within the three-dimensional frameworks whereas F-MOF-3 displays mononuclear SBUs and forms a one-dimensional chain. F-MOF-4 display a interesting 2D framework with conventional Cu(2)(CO(2))(4) paddle wheel SBU. In the crystal structures four hfbba ligands, each coordinated to a dicopper paddlewheel unit via one of their carboxylate groups. Solid-state properties such as UV-vis and thermal stability of F-MOF-1-5 have also been studied.

Amino functionalized zeolitic tetrazolate framework (ZTF) with high capacity for storage of carbon dioxide - Panda, Tamas; Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Chemical Communications, 2011)
A three dimensional -NH(2) functionalized Zeolitic Tetrazolate Framework (ZTF-1) has been reported. The framework adopts a dia topology (M-L-M angle is close to 156 degrees). ZTF-1 shows high CO(2) (273 K) and H(2) (77 K) uptake due to the presence of the free -NH(2) group and uncoordinated tetrazolate nitrogen.

Design and in situ synthesis of a Cu-based porous framework featuring isolated double chain magnetic character - Dey, Chandan; Das, Raja; Saha, Binoy Krishna; Poddar, Pankaj; Banerjee, Rahul (Chemical Communications, 2011)
A Cu-based double chain MOF was synthesized in hydrothermal conditions using an in situ ligand formation method. This double chain MOF shows temperature dependent ferromagnetic (long range ordering) and antiferromagnetic (intra double chain) coupling. The magnetic behaviour originating from the individual double chain remains almost same even after structural collapse due to the removal of guest water molecules.

Enhanced DSSC performance with high surface area thin anatase TiO2 nanoleaves - Dhas, Vivek V.; Muduli, Subas; Agarkar, Shruti A.; Rana, Abhimanyu; Hannoyer, Beatrice; Banerjee, Rahul; Ogale, Satishchandra B. (Solar Energy, 2011)
Thin anatase TiO2 nanoleaves (NLs) with high surface area (similar to 93 m(2)/g) are synthesized by hydrothermal route and dye-sensitized solar cells (DSSC) made using such NLs are compared with those made with hydro-thermally synthesized TiO2 nanoparticles and the Degussa P25 powder. The NLs-based DSSCs show increment of 16% and 24% in the total conversion efficiency over the cells made with NPs and P25 respectively. Interestingly, the highest increment in the conversion efficiency (similar to 35%) is achieved for cells made using a 50:50 (wt/wt) mixture of NLs and NPs. In this case the dye loading is found to be >50% higher than the case of NP films. Moreover the DC resistance of diffusion of I-3(-) in electrolyte (as revealed by the electrochemical impedance spectroscopy) is substantially lower than the NP film case, other cell parameters being nominally comparable. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dye-sensitized solar cells; Electrochemical impedance spectroscopy; hydrothermal

Experimental and computational approach of understanding the gas adsorption in amino functionalized interpenetrated metal organic frameworks (MOFs) - Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Journal of Materials Chemistry, 2011)
Two isostructural, three dimensional, interpenetrated, amino (-NH2) functionalized Metal Organic Frameworks [Cd(ANIC)(2)] (Cd-ANIC-1) and [Co(ANIC)(2)] (Co-ANIC-1) with amine-lined pores have been reported. The framework adopts dia topology with interpenetration. Cd-ANIC-1 and Co-ANIC-1 show high CO2 (273 K) and H-2 (77 K) uptake due to the presence of free -NH2 groups and framework interpenetration. The effect of interpenetration and amino functionalization on gas uptake properties of MOFs has been analysed experimentally and computationally, in the isostructural MOFs Cd-ANIC-1 and Co-ANIC-1.

Fe(III) complex of biuret-amide based macrocyclic ligand as peroxidase enzyme mimic - Panda, Chakadola; Ghosh, Munmun; Panda, Tamas; Banerjee, Rahul; Sen Gupta, Sayam (Chemical Communications, 2011)
An Fe(III) complex of a biuret-amide based macrocyclic ligand that exhibits both excellent reactivity for the activation of H(2)O(2) and high stability, especially at low pH and high ionic strength, is reported.

Helical water chain mediated proton conductivity in homochiral metal-organic frameworks with unprecedented zeolitic unh-topology - Sahoo, Subash Chandra; Kundu, Tanay; Banerjee, Rahul (Journal of the American Chemical Society, 2011)
Four new homochiral metal-organic framework (MOF) isomers, [Zn(l-L-Cl)(Cl)](H2O)(2) (1), [Zn(l-L-Br)(Br)]-(H2O)(2) (2), [Zn(d-L-Cl)(Cl)(H2O)(2) (3), and [Zn(d-L-Br)-(Br)] (H2O)(2) (4) [L = 3-methyl-2-(pyridin-4-ylmethylamino)-butanoic acid], have been synthesized by using a derivative of L-/D-valine and Zn(CH3COO)(2)center dot 2H(2)O. A three-periodic lattice with a parallel ID helical channel was formed along the crystallographic c-axis. Molecular rearrangement results in an unprecedented zeolitic unh-toparigy in 1-4. In each case, two lattice water molecules (one H-bonded. to halogen atoms) form a secondary helical continuous water chain inside the molecular helix. MOFs 1 and 2 shows different water adsorption properties and hence different water affinity. The arrangement of water molecules inside the channel Was monitored by variable temperature single crystal X-ray diffraction, which indicated that MOF 1 has a higher water holding capacity than MOF 2. In MOF 1, water escapes. at 80 degrees C, while in T the same happens at a much lower temperature (similar to 40 degrees C). All the MOFs reported here shows reversible crystallization by readily reabsorbing moisture. In MOFs 1 and 2, the frameworks are stable after solvent removal, which is confirmed by a single-crystal to single crystal transformation. MOFs 1 and 3 show high proton conductivity of 4.45 x 10(-5) and 4.42 x 10(-5) S cm(-1), respectively, while 2 and 4 shows zero proton conductivity. The above result is attributed to the fact that MOF 1 has a higher water holding capacity than MOF 2.

Hydrogen bond directed honeycomb-like porous network structure of tris (bipyridyl-glycoluril)cobalt(III) chloride - Kawade, Vitthal A.; Kumbhar, Avinash S.; Erxleben, Andrea; Pachfule, Pradip; Banerjee, Rahul (Crystengcomm, 2011)
The [Co(bpg)3]Cl-3 complex (1), where bpg = 4b, 5, 7, 7a-tetrahydro4b,7a-epiminomethan-oimino-6H-imidazo [4,5-f][1,10]-phenanthroline-6,13-dione has been synthesized and characterized by various spectroscopic techniques and single crystal X-ray diffraction. The combination of bipyridyl-glycoluril (bpg) ligands and cobalt ion self-organise to form a honeycomb-like porous network structure resulting in the formation of zeolite like channels which adsorb gases, is described.

Porous nitrogen rich cadmium-tetrazolate based metal organic framework (MOF) for H-2 and CO2 uptake - Pachfule, Pradip; Banerjee, Rahul (Crystal Growth & Design, 2011)
The highly porous nitrogen rich metal organic framework [Cd-3(4-TP)(6)] (Cd-4TP-1) was synthesized solvothermally from the predesigned organic building block 4-tetrazole pyridine (4-TP) and Cd(II) as metal center using DMF as solvent. Cd-4TP-1 has a three-dimensional porous architecture where all the binding sites of Cd(II) are exclusively occupied by the nitrogen atoms from the mu(2)-tetrazolyl group or the pyridyl functionality of the 4-TP ligands. Cd-4TP-1 has Brunauer-Emmett-Teller (BET) and Langmuir surface areas of 472.2 and 728.6 m(2)/g, respectively, and shows 1.1 wt % H-2 (77 K) and 2.7 mmol/g CO2 uptake (273 K).

Solvothermal synthesis, structure, and properties of metal organic framework isomers derived from a partially fluorinated link - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2011)
Solvothermal reactions of Cu(NO3)(2) center dot 3H(2)O with 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C17H10F6O4, H(2)hfbba) and terminal monodentate ligand 3-methyl pyridine (3-picoline/3-mepy) in the presence of N, N-dimethyl formamide (DMF) and N,N-diethyl formamide (DEF) solvents gave rise to two structurally different two-dimensional (2D) fluorinated metal organic frameworks (F-MOFs). The effect of the choice of solvent has been clearly reflected in the structures obtained. The F-MOFs reported in this paper are formulated as [Cu-2(hfbba)(2)(3-mepy)(2)] center dot (DMF)(2)(3-mepy) (F-MOF-4), [Cu-2(hfbba)(2)(3-mepy)(2)] (Cu-F-MOF-4B), and [Zn-2(hfbba)(2)(3-mepy)(2)] center dot (3-mepy) (Zn-F-MOF-4B) which displays interesting 2D structures with and without interdigitation depending on the solvent used. The structures of these F-MOFs have been determined by X-ray crystallography and further identified by IR spectroscopy, powder X-ray diffraction (PXRD), and thermogravimetric analysis (TGA). The effect of interdigitation has been reflected in the gas adsorption and magnetic properties of these F-MOFs. These F-MOFs also show comparable H-2 and CO2 uptake depending on their structural variation. Temperature-dependent magnetic susceptibility measurements over a wide range of temperatures exhibit dominantly short-range antiferromagnetic behavior, with weak ferromagnetic behavior showing up at very low temperatures, which is evident from opening of the hysteresis loop with a finite value of coercivity in both F-MOF-4 and Cu-F-MOF-4B. We observed a smaller value of mu(eff) per Cu atom and coercivity in Cu-F-MOF-4B than the F-MOF-4 due to relatively larger distances between the neighboring dicopper paddlewheel secondary building unit.

Structural and gas adsorption study of a two-dimensional copper-tetrazole based metal-organic framework - Pachfule, Pradip; Banerjee, Rahul (Current Science, 2011)
A new two-dimensional (2D) metal organic framework, Cu-1(4-TBA)(1)(DMBP)(1).DMF (Cu-TBA-3), has been synthesized under solvothermal condition from transition metal cation Cu(II), predesigned ligand 4-(1H-tetrazole-5-yl)benzoic acid (4-TBA) and coligand 4,4'-dimethy1-2,2'-bipyridine (DMBP). The structure has been determined by single crystal X-ray crystallography which shows layered 2D structure with square shaped one-dimensional channels. Cu-TBA-3 shows 0.69 wt% H-2 (at 77 K, 1 atm) and 1.65 mmol/g CO2 (at 298 K, 1 atm) uptake.
Keywords: CO2 capture; Hydrogen storage; metal-organic frameworks; microporous materials

Structural and selective gas adsorption studies of polyoxometalate and tris(ethylenediamine) cobalt(III) based ionic crystals - Dey, Chandan; Das, Raja; Pachfule, Pradip; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2011)
Seven new ionic solids built on polyoxometalate anions and [Co(en)(3)](3+) cations, namely, [Co(en)(3)Mo(8)O(26)(H(3)O)-(Cl)](DMF)(4)(H(2)O) (Co-Mo(8)-DMF), [alpha-PW(12)O(40)][Co(en)(3)]center dot 6DMF (Co-W(12)P-DMF), [alpha-PW(12)O(40)][Co(en)(3)]center dot 6DEF (Co-W(12)P-DEF), [alpha-PMo(12)O(40)][Co(en)(3)]center dot 5.5DMF (Co-Mo(12)P-DMF), [alpha-PMo(12)O(40)][Co(en)(3)]center dot 6DEF (Co-Mo(12)P-DEF), [alpha-SiW(12)O(40)]-[Co(en)(3)](3/2)[Cl](1/2)center dot 6DMF center dot 3H(2)O (Co-W(12)Si-DMF), and [alpha-SiW(12)O(40)][Co(en)(3)]center dot 6DEF (Co-W(12)Si-DEF), have been synthesized from nonaqueous (DMF/DEF) media and characterized by single-crystal X-ray diffraction. We attempt to understand if [Co(en)(3)](3+) cations used in these reaction systems play a crucial role in controlling the assembly of these crystals. These ionic solids, after removal of the DMF or DEF molecules, are found to exhibit size selective H(2) adsorption properties over N(2). The amount of hydrogen adsorption was influenced by POM anion types and their orientations. CoMo(12)P-DEF has the highest (0.9 wt %) H(2) uptake, and CoW(12)P-DEF has the lowest (0.4 wt %) uptake among the series when the adsorbate pressure approached 1 atm.

Structural isomerism and effect of fluorination on gas adsorption in copper-tetrazolate based metal organic frameworks - Pachfule, Pradip; Chen, Yifei; Sahoo, Subash Chandra; Jiang, Jianwen; Banerjee, Rahul (Chemistry of Materials, 2011)
Synthesis, structure, and gas adsorption properties of three Metal Organic Frameworks (MOFs) synthesized from predesigned ligands 4-(1H-tetrazole-5-yl)benzoic acid (4-TBA) and 2-fluoro-4-(1H-tetrazole-5-yl)benzoic acid (2F-4-TBA) along with Cu(II) as an metal precursor has been reported. Among these MOFs, Cu-9(4-TBA)(10)(C2H5OH)(2) (Cu-TBA-1) and Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) are structural isomers. Whereas, Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) and Cu-2(2-F-4-TBA)(2)(DMF)(2) (Cu-TBA-2F) have similar crystal structure. N-2 adsorption isotherms of the activated sample of Cu-TBA-1 and -2 exhibit types-I sorption behavior with a Langmuir and Brunauer-Emmett-Teller (BET) surface area of 686, 402 m(2)/g and 616, 356 m(2)/g, respectively. It is noteworthy that Cu-TBA-1 and -2 adsorbs 1.16 and, 1.54 wt % H-2, while Cu-TBA-2F adsorbs 0.67 wt % at 77 K and 1 atm. On the other hand, Cu-TBA-1 and -2 adsorb 3.08 and 2.54 mmol/g, while Cu-TBA-2F adsorbs 1.27 mmol/g of CO2 at 298 K and 1 bar pressure. H-2 adsorption sites in Cu-TBA-2 and -2F have been analyzed by molecular simulation.
Keywords: CO2 adsorption; fluorination; Hydrogen storage; Metal-organic framework; structural isomerism

Structural, magnetic, and gas adsorption study of a series of partially fluorinated metal-organic frameworks (HF-MOFs) - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Inorganic Chemistry, 2011)
Four new partially fluorinated metal organic frameworks (HF-MOFs) have been synthesized under different solvothermal conditions (H2O or dimethylformamide (DMF)) from transition metal cations [Co2+ and Mn2+], 3-methyl pyridine (3-mepy) and 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C17H10F6O4, H(2)hfbba), to determine the influence of reaction conditions on the formation of MOFs. This family of materials displays a striking degree of structural similarity depending on the solvent of synthesis. HF-MOFs synthesized from H2O [Co-HFMOF-W, Co(liffiba)(3-mepy)(H2O) and Mn-HFMOF-W, Mn(hfbba)(3-mepy)(H2O)] contain three-dimensional connectivity whereas HF-MOFs synthesized from DmF Co-HFMOF-D, [Co-2(hfbba)(2)(3-mepy)(2)]center dot(DMF)(3) and Mn-HFMOE-D, [Mn-2(hfbba)(2)(3-mepy)]center dot(H2O) are two-dimensional in nature. Co-HFMOF-W and Mn-HFMOF-W are iso-structural polymeric materials. Thermal gravimetric analysis performed on as-synthesized HP-MOFs revealed that these compounds have high thermal stability (similar to 350 degrees C). The continuous decrease of the chi T product with decreasing T for Co-HFMOF-D and Co-HFMOF-W respectively indicates the presence of antiferromagnetic exchange interaction between two Co2+ (S = 3/2) metal centers within a duster.

Structure and gas sorption behavior of a new three dimensional porous magnesium formate - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Inorganic Chemistry, 2011)
A new three-dimensional magnesium formate polymorph, namely, gamma-[Mg-3(O2CH)(6)] has been synthesized via in situ formate anion generation method. gamma-Mg-formate crystallizes in space group Pbcn, and structural determination by X-ray single crystal diffraction reveals a three-dimensional network of Mg2+ linked by formate anions. All formate anions possess similar binding mode to the metal center with one oxygen of a particular formate anion binds to one metal center (mu(1) oxygen) and other oxygen binds to two metal centers (mu(2) oxygen). N-2 adsorption studies indicate that the framework displays permanent porosity. The specific surface area of gamma-Mg-formate (BET, 120 m(2) gm(-1)) is lower than the alpha- polymorph (BET, 150 m(2) gm(-1)). However, the initial hydrogen uptake of gamma-Mg-formate reached almost 1.0 wt % when the adsorbate pressure approached 760 Torr at 77 K. This is higher than the hydrogen uptake of alpha-Mg-formate (0.6 wt %). gamma-Mg-formate, shows a moderate affinity and capacity for CO2 (3.4 angstrom kinetic diameter) at 298 K. The CO2 uptake at 760 Torr is 2.01 mmol gm(-1)(47.0 cc gm(-1)). Although this CO2 uptake is somewhat modest, it compares well with the CO2 uptake of several Mg-MOFs and ZIFs reported in the literature.

Synthesis and structural characterization of a solvated dimorph of a hydrazonato-oxovanadium(v) complex with [OV(mu-O)VO] core - Mondal, Bipul; Banerjee, Rahul; Ghosh, Tapas (Journal of the Indian Chemical Society, 2011)
In this paper we report the synthesis and structural characterization of a different monoclinic variety of the title complex [V2O3(L)(2)], incorporating the doubly deprotonated benzoyl hydrazone of 5-chloro-2-hydroxyacetophenone (H2L) with P2(1)/c space group that showed some differences in bonding patterns in the solid state with respect to its another monoclinic variety with C2/c space group reported earlier.
Keywords: crystal structure; dimorphism; hydrazone complex; Oxovanadium(v) complex

Template induced structural isomerism and enhancement of porosity in manganese(II) based metal-organic frameworks (Mn-MOFs) - Panda, Tamas; Pachfule, Pradip; Banerjee, Rahul (Chemical Communications, 2011)
Three new metal-organic framework isomers have been synthesized by using the organic linker 5-triazole isophthalic acid and Mn(NO3)(2)center dot xH(2)O. Structural conversions from non-porous to porous MOFs due to the template effect have been observed. The cross-sectional pore apertures of the resulting Mn-MOFs are comparable to the molecular dimensions of the template (pyrazine and 4,40-bipyridine). The periodic increased porosity in Mn-MOFs depending on the size of the template used has been further confirmed by the CO2 adsorption isotherms.

Alkali earth metal (Ca, Sr, Ba) based thermostable metal-organic frameworks (MOFs) for proton conduction - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (Chemical Communications, 2012)
{Three new alkaline earth metal based MOFs have been synthesized by using 4,4'-sulfobisbenzoic acid (SBBA) and alkaline earth metal salts M(NO3)(2)

Carbon dioxide capture by metal organic frameworks - Saha, Subhadeep; Chandra, Suman; Garai, Bikash; Banerjee, Rahul (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
The design and synthesis of functionalized metal organic framework materials (MOFs) for reversible physisorption of CO2 is discussed. This strategy of CO2 adsorption in MOFs requires less energy for regeneration than materials relying on chemisorption. As a result the MOFs have received considerable attention as sorbent materials for strategic gases such as CO2 and H,. In this review, we have discussed different MOFs and hybrid materials containing MOFs which can adsorb CO2 at room temperature. In order to achieve high adsorption capacity, fast CO2 adsorption-desorption and low energy requirement for regeneration are necessary. Several avenues for increasing the CO2 adsorption capacity of such materials, for instance, introduction of open metal sites and the use of ligand molecules with specific functionalities (like -OH or -NH2) have been described. It has been observed that CO2 loading capacity of MOFs increases with functionalization. Herein, we have discussed how N-containing and fluorinated MOFs are designed to achieve higher CO2 loading than their non-functionalized counterparts. Nanocarbons (e.g. carbon nanotubes, carbon nanofibres, etc.) are porous materials and a blend of these porous materials with porous MOFs or porous carbon derived from MOFs may act as a better adsorbate than even the pure materials. Enhancement of CO2 loading by nanocarbon-MOF hybrid material is also discussed.
Keywords: Carbon dioxide adsorbents; Carbon dioxide capture; hybrid materials; Metal organic frameworks; Nanocarbons; Porous nanocarbons

Competition between gelation and crystallisation of a peculiar multicomponent liquid system based on ammonium salts - Kapoor, Iti; Schoen, Eva-Maria; Bachl, Jurgen; Kuehbeck, Dennis; Cativiela, Carlos; Saha, Subhadeep; Banerjee, Rahul; Roelens, Stefano; Juan Marrero-Tellado, Jose; Diaz, David Diaz (Soft Matter, 2012)
An exemplar competition between gelation and crystallisation phenomena was examined with an unusual synergistic multicomponent (organo) gelator solution (MGS), which consists of a well-defined methanolic solution of (1R, 2R)-1,2-diaminocyclohexane L-tartrate containing 2.4 equiv. of concentrated hydrochloric acid. The optimal composition of the MGS was determined through meticulous solubility, gelation and structural studies, which support a transient gelation mechanism based on the kinetic self-assembly of the tartrate salt driven by hydrogen-bonding interactions, involving ammonium nitrogen donors and hydroxyl oxygen acceptors, and electrostatic interactions. The hydrochloric acid is involved in the solubilisation of the salt through an ionic dissociation-exchange process, which ends up with the formation-precipitation of (1R, 2R)-1,2-diaminocyclohexane dihydrochloride. As a consequence, an irreversible destruction of the gel takes place, which indicates the metastable nature of this phase that cannot be accessed from the thermodynamically equilibrated state. Gelation of a variety of oxygenated and nitrogenated solvents with moderate polarity occurred efficiently using extremely low MGS concentrations at low temperatures, and the gel phase was confirmed by dynamic rheological measurements. Several features make the described MGS unique: (1) it is a multicomponent solution where each component and its stoichiometry play a key role in the reproducible formation and stabilization of the gels; (2) it is formed by simple, small, and commercially available chiral building blocks (dissolved in a well-defined solvent system), which are easily amenable for further modifications; (3) the gelation phenomenon takes place efficiently at low temperature upon warming up the isotropic solution, conversely to the typical gel preparation protocol; and (4) the formed organogels are not thermoreversible despite the non-covalent interactions that characterize the 3D-network.

Control of porosity by using isoreticular zeolitic imidazolate frameworks (IRZIFs) as a template for porous carbon synthesis - Pachfule, Pradip; Biswal, Bishnu P.; Banerjee, Rahul (Chemistry-A European Journal, 2012)
Herein, by using isoreticular zeolitic imidazolate frameworks (IRZIFs) as a template, we report the synthesis, morphology, and gas adsorption properties of porous carbon synthesized by a nanocasting method at 1000 degrees C, in which furfuryl alcohol (FA) was used as a carbon source. By using IRZIFs with variable porosity as templates, we could achieve control over the carbon porosity and H-2 and CO2 uptake. The resultant microporous carbon C-70, synthesized by using ZIF-70 as the template, is the most porous (Brunauer-Emmett-Teller (BET) surface area 1510 m(2)g(-1)). Carbon C-68, synthesized by using ZIF-68, has moderate porosity (BET surface area 1311 m(2)g(-1)), and C-69, synthesized by using ZIF-69, has the lowest porosity in this series (BET surface area 1171 m(2)g(-1)). The porous carbons C-70, C-68, and C-69, which have graphitic texture, have promising H2 uptake capacities of 2.37, 2.15, and 1.96 wt%, respectively, at 77 K and 1 atm. Additionally, C-70, C-68, and C-69 show CO2 uptake capacities of 5.45, 4.98, and 4.54 mmolg(-1), respectively, at 273 K and 1 atm. The gas uptake trends shown by C-70, C-68, and C-69 clearly indicate the dependence of carbon porosity on the host template. Moreover, the as-synthesized carbons C-70, C-68, and C-69 show variable conductivity.
Keywords: Carbon; Hydrogen storage; metal-organic frameworks; microporous materials; zinc

Correlation between coordinated water content and proton conductivity in Ca-BTC-based metal-organic frameworks - Mallick, Arijit; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
Proton conductivity of five Ca-based MOFs which depends on the amount of water molecules coordinated to the Ca-centres has been reported. These MOFs show high temperature proton conductivity due to the strong hydrogen bonding between the lattice and coordinated water molecules.

Fine-tuning the balance between crystallization and gelation and enhancement of CO2 uptake on functionalized calcium based MOFs and metallogels - Mallick, Arijit; Schoen, Eva-Maria; Panda, Tamas; Sreenivas, K.; Diaz, David Diaz; Banerjee, Rahul (Journal of Materials Chemistry, 2012)
The synthesis, structure, gas adsorption and catalytic properties of a new 3D porous, crystalline metal-organic framework (Ca-5TIA-MOF) as well as stable viscoelastic metallogels (Ca-5TIA-Gel) are reported. Remarkably, the preparation of both types of materials can be carried out starting from the same organic ligand (i.e. 5-(1,2,4-triazoleyl) isophthalic acid (5TIA)), divalent metal ion (i.e. Ca(II)) and organic solvent (i.e. DMF). In this particular case, the presence of water in the solvent system favors the formation of a crystalline MOF, whereas a pure organic solvent induces gelation. The characterization of the materials was carried out using a series of techniques including XRD, FT-IR, TGA, TEM, SEM, SAXS and dynamic rheology. Experimental PXRD peaks of both Ca-5TIA-xerogel and Ca-5TIA-MOF matched reasonably well with simulated PXRD, suggesting the presence of, at least, some common structural elements in the 3D networks of both xerogel and crystalline phases. Moreover, the nature of the metal counteranion was found to have a critical influence on the gelation phenomenon. To the best of our knowledge, this report describes unprecedented Ca-based LMW-metallogels, as well as the first porous Ca-based MOF, which shows adsorption capacity for CO2 at 1 atm pressure. Interestingly, Ca-5TIA-xerogel presented 20% higher CO2-uptake than the crystalline Ca-5TIA-MOF at 1 atm and 298 K. Both Ca-5TIA-MOF and Ca-5TIA-Gel also displayed a modest catalytic activity towards the hydrosilylation of benzaldehyde, with slightly better performance for the gel phase material.

Fluorinated metal-organic frameworks: advantageous for higher H-2 and CO2 adsorption or not? - Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Chemistry-A European Journal, 2012)
The synthesis, structure, and gas adsorption properties of three new metalorganic frameworks (MOFs) designed from isonicotinic acid (INA) and its fluorinated analogue 3-fluoroisonicotinic acid (FINA) along with CoII as the metal center have been reported. Co-INA-1 ([Co3(INA)4(O)(C2H5OH)3][NO3].C2H5OH.3?H2O; INA=isonicotinic acid) and Co-INA-2 ([Co(INA)2].DMF) are structural isomers as are Co-FINA-1 ([Co3(FINA)4(O)(C2H5OH)2].H2O; FINA=3-fluoroisonicotinic acid) and Co-FINA-2 ([Co(FINA)2].H2O), but the most important thing to note here is that Co-INA-1 and Co-FINA-1 are isostructural as are Co-INA-2 and Co-FINA-2. The effect of partial introduction of fluorine atoms into the framework on the gas uptake properties of MOFs having similar structures has been analyzed experimentally and computationally in isostructural MOFs.
Keywords: cobalt; fluorine; Hydrogen storage; metal-organic frameworks; microporous materials; X-ray diffraction

Functionalized metal organic frameworks (MOFs) for reversible gas storage and sequestration applications - Banerjee, Rahul (Journal of the Indian Chemical Society, 2012)
The decreasing amount of fossil fuels and increasing threat of global warming from the pollutants have driven the search for clean energy source. Energy sources from fossil fuels still remain in the forefront despite being a major source of increased CO2 content in the atmosphere. Metal Organic Frameworks (MOFs) have emerged as promising materials for hydrogen storage and CO2 sequestration. Several factors influencing the hydrogen uptake of porous MOFs such as surface area, catenation, ligand functionalization, doping with alkali metals and unsaturated metal centers have been extensively studied. Similarly, well defined periodicity and tunable pore sizes along with less basic amino-functionalized MOFs enables them favorable for fast and reversible CO2 gas adsorption at low partial pressure and room temperature. In this review we present diverse aspects of metal organic frameworks like fluorination, amino functionalization for high hydrogen storage and CO2 sequestration capabilities.
Keywords: carbon capture; CO2 adsorption; fluorination; Hydrogen storage; Metal-organic framework; structural isomerism

Metal and metal oxide nanoparticle synthesis from metal organic frameworks (MOFs): finding the border of metal and metal oxides - Das, Raja; Pachfule, Pradip; Banerjee, Rahul; Poddar, Pankaj (Nanoscale, 2012)
Herein, for the first time, we report a generalized strategy for the successful synthesis of highly crystalline metal and metal oxide nanoparticles embedded in a carbon matrix by the controlled thermolysis of metal organic frameworks (MOFs). The rationalized synthesis strategy of a broad range of metal and metal oxides nanoparticles, such as Cu/CuO, Co/Co3O4, ZnO, Mn2O3, MgO and CdS/CdO, by thermolysis of MOFs demonstrates for the first time that metal ions with a reduction potential of -0.27 volts or higher present in MOFs always form pure metal nanoparticles during thermolysis in N-2, whereas metal ions with a reduction potential lower than -0.27 volts form metal oxide nanoparticles during thermolysis in N-2. Another point of interest is the fact that we have found a unique relationship between the nanoparticle size and the distance between the secondary building units inside the MOF precursors. Interestingly, the crystallinity of the carbon matrix was also found to be greatly influenced by the environment (N-2 and air) during thermolysis. Moreover, these nanoparticles dispersed in a carbon matrix showed promising H-2 and CO2 adsorption properties depending on the environment used for the thermolysis of MOFs.

Metal [Zn(II), Cd(II)], 1,10-phenanthroline containing coordination polymers constructed on the skeleton of polycarboxylates: synthesis, characterization, microstructural, and CO2 gas adsorption studies - Yadav, Pramod Kumar; Kumari, Niraj; Pachfule, Pradip; Banerjee, Rahul; Mishra, Lallan (Crystal Growth & Design, 2012)
{Four new coordination polymers have been obtained by the reaction of metal [Zn(II), Cd(II)], 1,10-phenanthroline separately with two carboxylic acids, [biphenyl-4,4'-dicarboxylic acid (4,4'-H(2)BDA),and 4,4'-azodibenzoic acid (4,4'-H(2)ADA)]. The crystal structures of the resulting complexes of type {[Zn(4,4'-BDA)(Phen)(2)center dot HCON(CH3)(2)}(n) (1), {[Cd(4,4'-BDA)(Phen)](2)center dot H2O\

Nitrogen-rich porous covalent imine network (CIN) material as an efficient catalytic support for C-C coupling reactions - Bhunia, Manas K.; Das, Swapan K.; Pachfule, Pradip; Banerjee, Rahul; Bhaumik, Asim (Dalton Transactions, 2012)
In an effort to expand the realm of possibilities of nitrogen-rich porous materials that could be used in catalysis, herein we report the synthesis of a new highly nitrogen rich (ca. 45%) porous covalent imine network (CIN-1) material employing simple Schiff base chemistry and further grafting its surface with palladium. Pd-loaded CIN-1 support acts as a truly heterogeneous catalyst towards Suzuki C-C coupling reaction between aryl halides with arylboronic acids. High surface area and excellent accessibility of the catalytic sites make it very efficient for heterogeneous catalysis. The stability of the catalyst due to intimate contact between nitrogen-rich organic support and metal allows several reuses with only a minor loss in catalytic activity.

One-dimensional confinement of a nanosized metal organic framework in carbon nanofibers for improved gas adsorption - Pachfule, Pradip; Balan, Beena K.; Kurungot, Sreekumar; Banerjee, Rahul (Chemical Communications, 2012)
The loading of a Zn-terephthalate based MOF in the inner cavity as well as on the outer walls of a hollow carbon nanofiber (CNF) creates MOF@CNF hybrids. This hybrid ``MOF@CNF'' displayed improved thermal stability as well as gas adsorption compared to the individual counterparts.

Polymorphs, salts, and cocrystals: what's in a name? - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)
The December 2011 release of a draft United States Food and Drug Administration (FDA) guidance concerning regulatory classification of pharmaceutical cocrystals of active pharmaceutical ingredients (APIs) addressed two matters of topical interest to the crystal engineering and pharmaceutical science communities: (1) a proposed definition of cocrystals; (2) a proposed classification of pharmaceutical cocrystals as dissociable ``API-excipient'' molecular complexes. The Indo U.S. Bilateral Meeting sponsored by the Indo-U.S. Science and Technology Forum titled The Evolving Role of Solid State Chemistry in Pharmaceutical Science was held in Manesar near Delhi, India, from February 2-4, 2012. A session of the meeting was devoted to discussion of the FDA guidance draft. The debate generated strong consensus on the need to define cocrystals more broadly and to classify them like salts. It was also concluded that the diversity of API crystal forms makes it difficult to classify solid forms into three categories that are mutually exclusive. This perspective summarizes the discussion in the Indo-U.S. Bilateral Meeting and includes contributions from researchers who were not participants in the meeting.

Polymorphs, salts and cocrystals: what's in a name? (vol 12, pg 2147, 2012) - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)

Porous ZnO nanorod for targeted delivery of doxorubicin: in vitro and in vivo response for therapeutic applications - Mitra, Shouvik; Subia, B.; Patra, Prasun; Chandra, Sourov; Debnath, Nitai; Das, Sumistha; Banerjee, Rahul; Kundu, Subhas C.; Pramanik, Panchanan; Goswami, Arunava (Journal of Materials Chemistry, 2012)
Cancer cell specific targeted delivery (TDD) by porous nanocarrier is on a high role. Here in a simple route for the synthesis of porous ZnO nanorods (ZnO) has been demonstrated. ZnO expressed very high surface area of 305.14 m(2) g(-1) (S-BET) and uniformly distributed pores of 5 nm. In continuation ZnO has been fabricated with 3-aminophosphonic acid followed by folic acid to yield folate conjugated porous ZnO nanorod (ZnO-FA). High surface area, uniformly distributed pores on its surface make the nanocarrier suitable for high drug loading (88%) of the anticancer drug doxorubicin (DOX). A pH triggered drug release was observed with minimum release in pathophysical conditions. In vitro efficacy of DOX loaded ZnO-FA (ZnO-FA-DOX) has been evaluated against breast cancer cells MDA-MB-231, which is not possible alone by DOX or ZnO-FA. Targeted scaffold with pendant -NH2 group has been covalently bonded with fluorescent dye (RITC) for cellular uptake and imaging studies in MDA-MB-231 cells; the possible pathway for cancer regression has also been evaluated. Even in vivo acute and intravenous toxicological evaluation on murine model system complemented biocompatibility of ZnO-FA in TDD. All together we have collaged a template free synthesis of porous ZnO nanorod, successful targeting on to cancer cells, high drug loading, pH triggered drug release, in vitro efficacy of ZnO-FA-DOX against MDA-MB-231 cells and in vivo compatibility as well. We envisioned the future prospect of porous ZnO nanostructures in TDD.

Rapid microwave synthesis of fluorescent hydrophobic carbon dots - Mitra, Shouvik; Chandra, Sourov; Kundu, Tanay; Banerjee, Rahul; Pramanik, Panchanan; Goswami, Arunava (RSC Advances, 2012)
Fluorescent hydrophobic carbon dots (HCDs) have been fabricated from a poloxamer by a simple microwave assisted process within a few minutes for the first time. Small and distinct spherical HCDs emitted bright blue and green fluorescent light depending upon the excitation wavelength and were dispersed easily in a wide variety of organic solvents. HCDs exhibited excellent water resistant behavior with a contact angle of similar to 122 degrees enforcing good hydrophobic character which will be quite useful in potential surface applications.

Reversible phase transformation in proton conducting strandberg-type POM based metal organic material - Dey, Chandan; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
A Cu(II)-phenanthroline connected Strandberg-type polyoxometalate based proton conducting MOF, Cu3Mo5P2, that contains one dimensional parallel water channels has been reported. Cu3Mo5P2 shows proton conduction at room temperature as well as elevated temperature.

Self-assembled one dimensional functionalized metal-organic nanotubes (MONTs) for proton conduction - Panda, Tamas; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
Two self-assembled isostructural functionalized metal-organic nanotubes have been synthesized using 5-triazole isophthalic acid (5-TIA) with In(III) and Cd(II). In-and Cd-5TIA possess one-dimensional (1D) nanotubular architecture and show proton conductivity along regular 1D channels, measured as 5.35 x 10(-5) and 3.61 x 10(-3) S cm(-1) respectively.

Solid phase morphological diversity of a rare vanadium cubane (V4O16) based metal organic framework - Dey, Chandan; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2012)
A Cu(II) connected V4O16-cubane based metal organic framework, Cu-2(phen)(2)(V4O8) (PO4)(4) [Cu2V4O16-2D] was synthesized under hydrothermal conditions. This is the first example of transition metal connected V4O16-cubane based MOF. X-ray single crystal data shows the alternate arrangement V4O16-cubane and Cu(phen)(O)(3) square pyramidal unit in two dimensions. These two-dimensional sheets are stacked on top of each other to form a three-dimensional architecture. Cu2V4O16-2D shows two types of solid state morphologies of the same phase, which was confirmed by scanning electron microscopy. It is noteworthy that this type of morphological difference of the solid phase in an extended metal organic hybrid material is rare and has not been perceived in the polyoxovanadate based MOFs literature. Cu2V4O16-2D was further characterized by powder X-ray diffraction (PXRD), thermal gravimetric analysis (TGA), IR-spectroscopy, scanning electron microscopy (SEM), and elemental analysis. We also studied the static magnetic and gas adsorption properties for Cu2V4O16-2D.

Solid-state thermolysis of anion induced metal-organic frameworks to ZnO microparticles with predefined morphologies: facile synthesis and solar cell studies - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (Crystal Growth & Design, 2012)
Simple one-step solid state thermolysis of two Zn-based homochiral metal organic frameworks (MOFs) leads to a dramatic difference in morphologies which depends on the anion (-Cl and -Br) and calcination environment (air and N-2). Rod-shaped (aspect ratio similar to 20), hexagonal column shaped (aspect ratio similar to 3), and elliptical aggregation of ZnO morphologies (aspect ratio similar to 3) are obtained and characterized. Although these two MOFs possess similar rod-shaped morphology, they produce dramatic change in resulting ZnO microparticle morphologies (from rod-shaped ZnO microparticles in the case of thermolysis of MOP 1 to hexagonal column shaped ZnO microparticles in the case of MOF 2 thermolysis) when calcined in N-2 at 800 degrees C. However, when we calcined both MOF 1 and 2 in air, we encountered similar elliptical aggregation of ZnO microparticles. These ZnO microparticles show permanent porosity, visible light emission centered at 605 or 510 nm. Moreover, they show 0.15% and 0.14% dye sensitized solar cell activity. To the best of our knowledge, this is the first report of dye sensitized solar cell activity of ZnO microparticles obtained from one-step thermolysis of porous homochiral MOFs.

Solution mediated phase transformation (RHO to SOD) in porous Co-imidazolate based zeolitic frameworks with high water stability - Biswal, Bishnu P.; Panda, Tamas; Banerjee, Rahul (Chemical Communications, 2012)
Here we report a highly porous, water stable Co based ZIF [CoNIm (RHO)] and its solution mediated phase transformation to a less porous and water unstable ZIF [CoNIm (SOD)]. CoNIm (RHO) has high Langmuir surface area [2087 m(2) g(-1)] as well as high water adsorption [200 cm(3) (STP) g(-1)] capacity.

Variable water adsorption in amino acid derivative based homochiral metal organic frameworks - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (Crystal Growth & Design, 2012)
{Six new Cd-containing homochiral metal organic framework materials [

Chemically stable multilayered covalent organic nanosheets from covalent organic frameworks via mechanical delamination - Chandra, Suman; Kandambeth, Sharath; Biswal, Bishnu P.; Lukose, Binit; Kunjir, Shrikant M.; Chaudhary, Minakshi V.; BabaRao, Ravichandar; Heine, Thomas; Banerjee, Rahul (Journal of the American Chemical Society, 2013)
A series of five thermally and chemically stable functionalized covalent organic frameworks (COFs), namely, TpPa-NO2, TpPa-F-4, TpBD-(NO2)(2), TpBD-Me-2, and TpBD-(OMe)(2) were synthesized by employing the solvothermal aldehyde-amine Schiff base condensation reaction. In order to complete the series, previously reported TpPa-1, TpPa-2, and TpBD have also been synthesized, and altogether, eight COFs were fully characterized through powder X-ray diffraction (PXRD), Fourier transform IR (FT-IR) spectroscopy, C-13 solid-state NMR spectroscopy, and thermogravimetric analysis. These COFs are crystalline, permanently porous, and stable in boiling water, acid (9 N HCl), and base (3 N NaOH). The. synthesized COFs (all eight) were successfully delaminated using a simple, safe, and environmentally friendly mechanical grinding route to transform into covalent organic nanosheets (CONs) and were well characterized via transmission electron microscopy and atomic force microscopy. Further PXRD and FT-IR analyses confirm that these CONs retain their structural integrity throughout the delamination process and also remain stable in aqueous, acidic, and basic media like the parent COFs. These exfoliated CONs have graphene-like layered morphology (delaminated layers), unlike the COFs from which they were synthesized.

Controlled synthesis of a catalytically active hybrid metal-oxide incorporated zeolitic imidazolate framework (MOZIF) - Dey, Chandan; Banerjee, Rahul (Chemical Communications, 2013)
A rare hybrid Metal-Oxide incorporated Zeolitic Imidazolate Framework, MOZIF-1, containing tetrahedral Zn(II) and Mo(VI) centres has been synthesized. MOZIF-1 can degrade methyl orange and orange II dyes under visible light. Na-3[PMo12O40] is the source of Mo(VI) in MOZIF-1.

Electron rich porous extended framework as a heterogeneous catalyst for Diels-Alder reactions - Gole, Bappaditya; Bar, Arun Kumar; Mallick, Arijit; Banerjee, Rahul; Mukherjee, Partha Sarathi (Chemical Communications, 2013)
An electron rich porous metal-organic framework (MOF) has been synthesized, which acts as an effective heterogeneous catalyst for Diels-Alder reactions through encapsulation of the reactants in confined nano-channels of the framework.

Enhancement of chemical stability and crystallinity in porphyrin-containing covalent organic frameworks by intramolecular hydrogen bonds - Kandambeth, Sharath; Shinde, Digambar Balaji; Panda, Manas K.; Lukose, Binit; Heine, Thomas; Banerjee, Rahul (Angewandte Chemie-International Edition, 2013)
Keywords: covalent organic frameworks; hydrogen bonds; mesoporous materials; porphyrinoids; tautomerism

Four 3D Cd(II)-based metal organic hybrids with different N,N `-donor spacers: syntheses, characterizations, and selective gas adsorption properties - Bhattacharya, Biswajit; Dey, Rajdip; Pachfule, Pradip; Banerjee, Rahul; Ghoshal, Debajyoti (Crystal Growth & Design, 2013)
{Four new metal organic frameworks with bivalent cadmium, disodium succinate (Na(2)suc), and four different N,N'-donor ligands, i.e., {[Cd(L1)(suc)]center dot(H2O)(3)}(n) (1), {[Cd(L2)(suc)]center dot(H2O)(2)\

Hydrolytic conversion of a metal-organic polyhedron into a metal-organic framework - Mallick, Arijit; Garai, Bikash; Diaz, David Diaz; Banerjee, Rahul (Angewandte Chemie-International Edition, 2013)
Keywords: cage compounds; crystal engineering; hydrophobic effect; metal-organic frameworks; Self-assembly

In situ growth of metal-organic frameworks on a porous ultrafiltration membrane for gas separation - Nagaraju, Divya; Bhagat, Deepti G.; Banerjee, Rahul; Kharul, Ulhas K. (Journal of Materials Chemistry A, 2013)
We demonstrate the synthesis of CuBTC and ZIF-8 on a polysulfone based porous asymmetric ultrafiltration (UF) membrane by in situ growth followed by the LBL deposition of crystals without any need for preseeding or surface modification of the membrane. In this way, the top surface of the UF membrane pores is completely covered by MOFs; while the remaining part of the membrane offers a flexible support to the MOFs. The pore apertures of the MOF nanoparticles located at the pore opening of the UF membrane act as channels for the entry of penetrants. The remaining porous sublayer of the membrane carries penetrants on the permeate side without significant resistance. These composite membranes were characterized by PXRD and SEM. The gas permeation study was performed using pure gases of industrial significance (H-2, C3H6 and CO2). The performance of CuBTC@PSF showed enhanced selectivity, of 7.2 and 5.7 for H-2/CO2 and H-2/C3H6 respectively, to that of the pristine PSF membrane.

POM-catalyzed in situ ligand synthesis for the construction of metal complexes and their use in the formation of coordination polymers - Dey, Chandan; Banerjee, Rahul (Chemphyschem, 2013)
Six organicinorganic hybrid materials were synthesized by the in situ oxidation of neocuproine by using MoO3/Na2MoO4 as the catalyst in the presence of Cu(NO3)2. The crystal structures of Mo8-Cu4-PHEN and Mo8-Cu2-5(2PIC) are composed of [Mo8O26]4 polyoxometalate (POM) units, whereas the crystal structure of Mo6-Cu-COPHEN is composed of a [Mo6O19]2 POM unit; both POM units could be considered as the active form of the catalyst. Reaction of the hybrid materials with 1,3,5-benzenetricarboxylic acid (BTC) resulted in the formation of two different coordination polymers (CPs) under different reaction conditions. These CPs, depending on their structural attributes, exhibit distinct differences in the adsorption of H2, CO2, and water. The use of 2-methylpyridine instead of neocuproine does not give any oxidation products under the same reaction conditions due to the incorrect positioning of the methyl group with respect to the CuII center.
Keywords: coordination polymers; Copper; N ligands; organicinorganic hybrid composites; polyoxometalates

Porous carbons from nonporous MOFs: influence of ligand characteristics on intrinsic properties of end carbon - Aiyappa, Harshitha Barike; Pachfule, Pradip; Banerjee, Rahul; Kurungot, Sreekumar (Crystal Growth & Design, 2013)
Synthesis of porous carbons on direct carbonization of nonporous Zn-based MOFs has been achieved without using any additional carbon precursor. The effect of ligand nature on the resulting carbon porosity has been studied systematically using the MOFs synthesized from rigid and flexible ligands. The linear relations between Zn/C ratio of the MOF versus surface area of the resulting carbon, micro-porosity versus H-2 uptake achieved in these carbons, and surface area versus specific capacitance of the end carbons have been verified from the gas adsorption, molecular composition, and electrochemical studies, respectively. Cyclic voltammetry and charge-discharge cycling have been carried out to study the capacitive behavior of the carbons. The interdependence of capacitive behavior on the surface area has been analyzed using data derived from N-2 adsorption isotherms and charge-discharge curves. Among the carbons synthesized, C-MOF-2 shows maximal surface area of 1378 m(2)/g with a specific capacitance of 170 F/g at 1 A/g.

Porous-organic-framework-templated nitrogen-rich porous carbon as a more proficient electrocatalyst than Pt/C for the electrochemical reduction of oxygen - Pachfule, Pradip; Dhavale, Vishal M.; Kandambeth, Sharath; Kurungot, Sreekumar; Banerjee, Rahul (Chemistry-A European Journal, 2013)
Porous nitrogen-rich carbon (POF-C-1000) that was synthesized by using a porous organic framework (POF) as a self-sacrificing host template in a nanocasting process possessed a high degree of graphitization in an ordered structural arrangement with large domains and well-ordered arrays of carbon sheets. POF-C-1000 exhibits favorable electrocatalytic activity for the oxygen-reduction reaction (ORR) with a clear positive shift of about 40 mV in the onset potential compared to that of a traditional, commercially available Pt/C catalyst. In addition, irrespective of its moderate surface area (785 m2?g-1), POF-C-1000 showed a reasonable H2 adsorption of 1.6 wt?% (77 K) and a CO2 uptake of 3.5 mmol?g-1 (273 K).
Keywords: Adsorption; Electrochemistry; fuel cells; oxygen-reduction reaction; porous organic frameworks

Proton-conducting supramolecular metallogels from the lowest molecular weight assembler ligand: a quote for simplicity - Saha, Subhadeep; Schoen, Eva-Maria; Cativiela, Carlos; Diaz, David Diaz; Banerjee, Rahul (Chemistry-A European Journal, 2013)
Oxalic acid has been proven to be the lowest molecular weight organic ligand able to form robust supramolecular metallogel networks in the presence of metal salts. In particular, two novel multifunctional metallogels were readily prepared at room temperature by simple mixing of stock solutions of Cu-II acetate monohydrate or Cu-II perchlorate hexahydrate and oxalic acid dihydrate. Formation of different polymorphs and unprecedented proton conduction under anhydrous conditions were also demonstrated with some of these materials.
Keywords: Copper; low-molecular-weight ligands; metallogels; proton conductivity; supramolecular chemistry

Relating pore hydrophilicity with vapour adsorption capacity in a series of amino acid based metal organic frameworks - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (CrystEngComm, 2013)
A new Zn based porous homochiral metal-organic framework, ThrZnOAc, belonging to unh topology, has been synthesized using pyridyl functionalized threonine and Zn(OAc)(2) as the metal precursor. Stepwise substitution of the homochiral MOF backbone by simply changing the sidearm of the amino acids (isopropyl in the case of valine, methyl in alanine and hydroxyethyl in threonine) resulted in increased water adsorption in ThrZnOAc compared to the previously reported ValZnOAc/AlaZnOAc. Extensive solvent sorption isotherms (water, methanol, isopropanol and toluene) have been carried out, which revealed high solvophilic interaction with polar solvents in ThrZnOAc due to the polar pore [2-hydroxyethyl {-CH(OH)CH3} sidearm of the amino acid], which is not prominent in the corresponding valine/alanine counterparts. The aforementioned functionalization in a series of isostructural amino acid based MOFs with the only difference being in the sidearm and their emergence as enhanced solvophilic materials is unprecedented in the MOF literature.

Salt metathesis in three dimensional metal-organic frameworks (MOFs) with unprecedented hydrolytic regenerability - Kundu, Tanay; Sahoo, Subash Chandra; Saha, Subhadeep; Banerjee, Rahul (Chemical Communications, 2013)
{Eight Zn-based porous (1.2 nm) homochiral MOFs (ValZnX, AlaZnX

Stabilization of graphene quantum dots (GQDs) by encapsulation inside zeolitic imidazolate framework nanocrystals for photoluminescence tuning - Biswal, Bishnu P.; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Banerjee, Rahul (Nanoscale, 2013)
Luminescent graphene quantum dots (GQDs) are encapsulated and stabilized in Zeolitic Imidazolate Framework (ZIF-8) nanocrystals. The GQDs are well confined due to the adsorption on the growing face of the ZIF-8 nanocrystals and have a profound effect on the shape of the nanocrystals from rhombic dodecahedron to spherical. Stabilizing GQDs inside the ZIF-8 nanocrystals results in tailoring of the photoluminescence emission (ca. 32 nm, bathochromic shift) of the GQD@ZIF-8 nanocrystal composite even after 3 months of aging under normal laboratory conditions. Also the water adsorption (at STP) capacity increased for the GQD@ ZIF-8 composite as compared to the pristine ZIF-8.

Structural design of coordination polymers - Du, Miao; Banerjee, Rahul; Shimizu, George K. H. (Crystengcomm, 2013)

Structural isomerism leading to variable proton conductivity in indium(III) isophthalic acid based frameworks - Panda, Tamas; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2013)
Proton conductivity has been studied thoroughly in two isomeric In(III)-isophthalate based MOFs. In-IA-2D-1 is capable of showing proton conductivity (3.4 x 10(-3) S cm(-1)) under humidified conditions (98% RH), whereas In-IA-2D-2 can conduct protons (2.6 x 10(-5) S cm(-1)) under humidified as well as anhydrous conditions.

Synthesis, structure, and H-2/CO2 adsorption in a three-dimensional 4-connected triorganotin coordination polymer with a sqc topology - Chandrasekhar, Vadapalli; Mohapatra, Chandrajeet; Banerjee, Rahul; Mallick, Arijit (Inorganic Chemistry, 2013)
A 4-connected triorganotin 3D coordination polymer in a sqc topology has been shown to possess 1D microchannels along its crystallographic a axis. This main-group-element-containing framework structure shows selective gas adsorption, preferring CO2 and H-2 over N-2.

Zeolitic imidazolate framework (ZIF)-derived, hollow-core, nitrogen-doped carbon nanostructures for oxygen-reduction reactions in PEFCs - Palaniselvam, Thangavelu; Biswal, Bishnu P.; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry-A European Journal, 2013)
The facile synthesis of a porous carbon material that is doped with iron-coordinated nitrogen active sites (FeNC-70) is demonstrated by following an inexpensive synthetic pathway with a zeolitic imidazolate framework (ZIF-70) as a template. To emphasize the possibility of tuning the porosity and surface area of the resulting carbon materials based on the structure of the parent ZIF, two other ZIFs, that is, ZIF-68 and ZIF-69, are also synthesized. The resulting active carbon material that is derived from ZIF-70, that is, FeNC-70, exhibits the highest BET surface area of 262m2g-1 compared to the active carbon materials that are derived from ZIF-68 and ZIF-69. The HR-TEM images of FeNC-70 show that the carbon particles have a bimodal structure that is composed of a spherical macroscopic pore (about 200nm) and a mesoporous shell. X-ray photoelectron spectroscopy (XPS) reveals the presence of Fe-N-C moieties, which are the primary active sites for the oxygen-reduction reaction (ORR). Quantitative estimation by using EDAX analysis reveals a nitrogen content of 14.5wt.%, along with trace amounts of iron (0.1wt.%), in the active FeNC-70 catalyst. This active porous carbon material, which is enriched with Fe-N-C moieties, reduces the oxygen molecule with an onset potential at 0.80V versus NHE through a pathway that involves 3.3-3.8e- under acidic conditions, which is much closer to the favored 4e- pathway for the ORR. The onset potential of FeNC-70 is significantly higher than those of its counterparts (FeNC-68 and FeNC-69) and of other reported systems. The FeNC-based systems also exhibit much-higher tolerance towards MeOH oxidation and electrochemical stability during an accelerated durability test (ADT). Electrochemical analysis and structural characterizations predict that the active sites for the ORR are most likely to be the insitu generated NFeN2+2/C moieties, which are distributed along the carbon framework.
Keywords: Doping; Electrochemistry; metal-organic frameworks; Nanostructures; oxygen-reduction reaction

2014 International year of crystallography celebration: India - Banerjee, Rahul (Crystengcomm, 2014)

Amino acid-based multiresponsive low-molecular weight metallohydrogels with load-bearing and rapid self-healing abilities - Saha, Subhadeep; Bachl, Jurgen; Kundu, Tanay; Diaz, David Diaz; Banerjee, Rahul (Chemical Communications, 2014)
A multiresponsive metallohydrogel based on an amino acid-derived low molecular weight (LMW) ligand and a Zn(II) salt was prepared. This hydrogel showed remarkable shape-persistent, self-standing, load-bearing and self-healing properties, which is uncommon in LMW hydrogels.

Chemically delaminated free standing covalent organic nanosheets (CONs) - Khayum, Abdul M.; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; porous polymers; ultra thin nano sheets

Chemically stable urea based COF for size selective heterogeneous catalysis - Basu, Arghya; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: chemical stability; Covalent organic framework; heterogeneous catalysis

Construction of highly crystalline ultraporous covalent organic frameworks in seconds - Karak, Suvendu; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: COFs; Crystalline; Ultraporous

Covalent organic framework thin-films for molecular separation - Dey, Kaushik; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; Separation; Thin-films

Covalent organic framework-cadmium sulfide hybrid as a prototype photocatalyst for visible-light-driven hydrogen production - Thote, Jayshri; Aiyappa, Harshitha Barike; Deshpande, Aparna; Diaz, David Diaz; Kurungot, Sreekumar; Banerjee, Rahul (Chemistry A-European Journal, 2014)
CdS nanoparticles were deposited on a highly stable, two-dimensional (2D) covalent organic framework (COF) matrix and the hybrid was tested for photocatalytic hydrogen production. The efficiency of CdS-COF hybrid was investigated by varying the COF content. On the introduction of just 1 wt% of COF, a dramatic tenfold increase in the overall photocatalytic activity of the hybrid was observed. Among the various hybrids synthesized, that with 10 wt% COF, named CdS-COF (90: 10), was found to exhibit a steep H2 production amounting to 3678 mmolh(-1) g(-1), which is significantly higher than that of bulk CdS particles (124 mmolh(-1)g(-1)). The presence of a p-conjugated backbone, high surface area, and occurrence of abundant 2D hetero-interface highlight the usage of COF as an effective support for stabilizing the generated photoelectrons, thereby resulting in an efficient and high photocatalytic activity.
Keywords: charge transfer; covalent organic frameworks; hybrid materials; hydrogen production; Photocatalysis

Crystalline metal-organic frameworks (MOFs): synthesis, structure and function - Dey, Chandan; Kundu, Tanay; Biswal, Bishnu P.; Mallick, Arijit; Banerjee, Rahul (Acta Crystallographica Section B-Structural Science, 2014)
Metal-organic frameworks (MOFs) are a class of hybrid network supramolecular solid materials comprised of organized organic linkers and metal cations. They can display enormously high surface areas with tunable pore size and functionality, and can be used as hosts for a range of guest molecules. Since their discovery, MOFs have experienced widespread exploration for their applications in gas storage, drug delivery and sensing. This article covers general and modern synthetic strategies to prepare MOFs, and discusses their structural diversity and properties with respect to application perspectives.

Crystalline porous materials for gas adsorption - Pal, Tapan Kumar; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; gas adsorption

Decoding the morphological diversity in two dimensional crystalline porous polymers - Halder, Arjun; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; Density functional calculations; Morphology

Dissolvable metallohydrogels for controlled release: evidence of a kinetic supramolecular gel phase intermediate - Saha, Subhadeep; Bachl, Jurgen; Kundu, Tanay; Diaz, David Diaz; Banerjee, Rahul (Chemical Communications, 2014)
Two metallohydrogels based on an amino acid-based ligand and Zn(II) salts were synthesized. These hydrogels show an uncommon, reversible, time-dependent transformation from the opaque to transparent state. These hydrogels also exhibit gradual dissolution in water (pH <= 7) over time. A water-soluble stimulant, caffeine, could be in situ loaded into the hydrogels and slowly released during dissolution.

Distinctive PdCl2-mediated transformation of Fe-based metallogels into metal-organic frameworks - Aiyappa, Harshitha Barike; Saha, Subhadeep; Garai, Bikash; Thote, Jayshri; Kurungot, Sreekumar; Banerjee, Rahul (Crystal Growth & Design, 2014)
Simple, efficient conversion of viable Fe3+-based metallogels into Fe-metal-organic frameworks (MOFs) has been achieved by PdCl2-mediated gel degradation. The metallogels and the resulting MOFs have been characterized, and a probable mechanism for the event has been elucidated.

Enhancement of CO2 uptake in iso-reticular Co based zeolitic imidazolate frameworks via metal replacement - Panda, Tamas; Gupta, Krishna M.; Jiang, Jianwen; Banerjee, Rahul (CrystEngComm, 2014)
Three Co based Zeolitic Imidazolate Frameworks (Co-ZIF-68, -69 and -81) which adopt a GME topology with high porosity have been synthesized. These Co-ZIFs show high CO2 (273 K/298 K) uptake compared to their isostructural Zn based analogues, which has been proved experimentally as well as by ab initio calculations.

Evolution of an adenine-copper cluster to a highly porous cuboidal framework: solution-phase ripening and gas-adsorption properties - Venkatesh, V.; Pachfule, Pradip; Banerjee, Rahul; Verma, Sandeep (Chemistry-A European Journal, 2014)
The synthesis and directed evolution of a tetranu-clear copper cluster, supported by 8-mercapto-N9-propyladenine ligand, to a highly porous three-dimensional cubic framework in the solid state is reported. The structure of this porous framework was unambiguously characterized by Xray crystallography. The framework contains about 62% solvent-accessible void; the presence of a free exocyclic amino group in the porous framework facilitates reversible adsorption of gas and solvent molecules. Oriented growth of framework in solution was also tracked by force and scanning electron microscopy studies, leading to identification of an intriguing ripening process, over a period of 30 days, which also revealed formation of cuboidal aggregates in solution. The elemental composition of these cuboidal aggregates was ascertained by EDAX analysis.
Keywords: cuboidal frameworks; gas adsorption; metal-organic frameworks; Ostwald ripening; solution-phase ripening

Flexible dicarboxylate based pillar-layer metal organic frameworks: differences in structure and porosity by tuning the pyridyl based N, N ` linkers - Dey, Rajdip; Bhattacharya, Biswajit; Pachfule, Pradip; Banerjee, Rahul; Ghoshal, Debajyoti (CrystEngComm, 2014)
{Dicarboxylate supported metal organic hybrids of Co(II), Zn(II) and Cd(II) have been synthesized using two different pyridyl based N, N' linkers having Schiff base functionalized site. The use of flexible dicarboxylate glutarate in designing such frameworks has created a marked diversity in topology. The different N, N' donor linkers also played an active part in the channel modification in the synthesized MOFs. The structural and topological diversity has been analyzed from the single crystal X-ray structure. Five compounds, {[Co(azpy)(glut)]center dot(CH3OH)}(n) (1), {[Co(meazpy)(glut)(H2O)(2)]center dot (H2O)(3)

High charge carrier mobility in two dimensional indium (iii) isophthalic acid based frameworks - Panda, Tamas; Banerjee, Rahul (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2014)
The effect of dimensionality (1D to 2D) on charge carrier mobility have been studied thoroughly on three In(III)-isophthalate based MOFs [In-IA-1D, In-IA-2D-1 and -2]. In-IA-1D possess 1D nanotubular architecture with [(CH3)(2)NH2](+). In-IA-2D-1 have 2D layers containing only [(CH3)(2)NH2](+) cations. Whereas, In-IA-2D-2 have [(CH3)(2)NH2](+) cations as well as solvent DMF molecule inside the crystal structure. Due to presence of the pi-pi stacking arrangement among the phenyl rings of IA moieties facilitates the high charge carrier mobility (4.6 x 10(-3) cm(2) V-1 s(-1) at V-G = -40 V) in In-IA-2D-2. However, In-IA-1D and In-IA-2D-1 does not show any charge carrier mobility due to absence of pi-pi stacking arrangement.
Keywords: Charge carrier mobility; Coordination chemistry; metal organic framework; pi-pi stacking

Highly stable covalent organic framework-Au nanoparticles hybrids for enhanced activity for nitrophenol reduction - Pachfule, Pradip; Kandambeth, Sharath; Diaz, David Diaz; Banerjee, Rahul (Chemical Communications, 2014)
{Gold [

Ligand-free one-step synthesis of 001 faceted semiconducting BiOCl single crystals and their photocatalytic activity - Biswas, Anupam; Das, Raja; Dey, Chandan; Banerjee, Rahul; Poddar, Panka (Crystal Growth & Design, 2014)
Herein, we report one-step ligand-free hydrothermal synthesis of predominantly {001}-faceted micron-sized single crystals of bismuth oxychloride (BiOCl). The structural chlorine is obtained by in situ generation of chloride ions. From Raman spectra, we could resolve the E-g transition. Photocatalytic activity of as-synthesized crystals showed 78% degradation of RhB dye under a xenon source after 120 min of exposure.

Mechanical downsizing of a gadolinium(iii)-based metal-organic framework for anticancer drug delivery - Kundu, Tanay; Mitra, Shouvik; Patra, Prasun; Goswami, Arunava; Diaz, David Diaz; Banerjee, Rahul (Chemistry-A European Journal, 2014)
A Gd-III-based porous metal-organic framework (MOF), Gd-pDBI, has been synthesized using fluorescent linker pDBI (pDBI=(1,4-bis(5-carboxy-1H-benzimidazole-2-yl)benzene)), resulting in a three-dimensional interpenetrated structure with a one-dimensional open channel (1.9x1.2nm) filled with hydrogen-bonded water assemblies. Gd-pDBI exhibits high thermal stability, porosity, excellent water stability, along with organic-solvent and mild acid and base stability with retention of crystallinity. Gd-pDBI was transformed to the nanoscale regime (ca. 140nm) by mechanical grinding to yield MG-Gd-pDBI with excellent water dispersibility (>90min), maintaining its porosity and crystallinity. In vitro and in vivo studies on MG-Gd-pDBI revealed its low blood toxicity and highest drug loading (12wt%) of anticancer drug doxorubicin in MOFs reported to date with pH-responsive cancer-cell-specific drug release.
Keywords: ball-milling; doxorubicin; drug delivery; metal-organic frameworks; nanocarriers

Mechanochemical synthesis of amide functionalized porous organic polymers - Rajput, Lalit; Banerjee, Rahul (Crystal Growth & Design, 2014)
Two porous organic polymers decorated with the amide functionality were synthesized mechanochemically and their properties were compared with the ones prepared by conventional solution mediated method. All the POPs were subjected to gas and water vapor sorption studies. The mechanochemically synthesized POPs have less surface area and show moderate adsorption properties compared to the solution mediated POPs. The amide based POPs show remarkable stability in water and concentrated acids.

Mechanosynthesis of imine, beta-ketoenamine, and hydrogen-bonded imine-linked covalent organic frameworks using liquid-assisted grinding - Das, Gobinda; Shinde, Digambar Balaji; Kandambeth, Sharath; Biswal, Bishnu P.; Banerjee, Rahul (Chemical Communications, 2014)
A variety of aromatic amines/hydrazides and aldehydes have been utilized for the construction of crystalline COFs at a faster rate and in high yield, irrespective of their reactivity and solubility using the Liquid-Assisted Grinding (LAG) method.

Multifunctional and robust covalent organic framework-nanoparticle hybrids - Pachfule, Pradip; Panda, Manas K.; Kandambeth, Sharath; Shivaprasad, S. M.; Diaz, David Diaz; Banerjee, Rahul (Journal of Materials Chemistry A, 2014)
Highly dispersed Pd(0) nanoparticles were successfully immobilized into a stable, crystalline and porous covalent organic framework (COF), TpPa-1, by a solution infiltration method using NABH(4) as a reducing agent. High resolution and dark field TEM images confirmed the uniform loading of the Pd(0) nanoparticles into the TpPa-1 matrix without aggregation. This hybrid material exhibited excellent catalytic activity towards the Cu free Sonogashira, Heck and sequential one pot Heck-Sonogashira cross-coupling reactions under basic conditions, and with superior performance compared to commercially available Pd supported on activated charcoal (i.e., 1, 5 and 10 wt%). Additionally, the precursor Pd(II)-doped COF also displayed competitive catalytic activity for the intramolecular oxidative biaryl synthesis under acidic conditions. Both catalysts were found to be highly stable under the reaction conditions showing negligible metal leaching, non-sintering behavior, and good recyclability. To the best of our knowledge, the organic support used in this work, TpPa-1, constitutes the first COF matrix that can hold both Pd(0) nanoparticles and Pd(II) complex without aggregation for catalytic purposes under both highly acidic and basic conditions.

Phosphoric acid loaded azo (-N=N-) based covalent organic framework for proton conduction - Chandra, Suman; Kundu, Tanay; Kandambeth, Sharath; BabaRao, Ravichandar; Marathe, Yogesh N.; Kunjir, Shrikant M.; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Two new chemically stable functional crystalline covalent organic frameworkds (COFs) (Tp-Azo and Tp-Stb) were synthesized using the Schiff base reaction between triformylphloroglucinol (Tp) and 4,4'-azodianiline (Azo) or 4,4'-diaminostilbene (Stb), respectively. Both COFs show the expected keto-enamine form, and high stability toward boiling water, strong acidic, and basic media. H3PO4 doping in Tp-Azo leads to immobilization of the acid within the porous framework, which facilitates proton conduction in both the hydrous (sigma = 9.9 X 10(-4) S cm(-1)) and anhydrous state (sigma = 6.7 X 10(-5) S cm-1). This report constitutes the first emergence of COFs as proton conducting materials.

Photocatalytic metal-organic framework from cds quantum dot incubated luminescent metallohydrogel - Saha, Subhadeep; Das, Gobinda; Thote, Jayshri; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Cadmium sulfide (CdS) quantum dots (<10 nm in size) have been successfully synthesized in situ without any capping agent in a Zn(II)-based low-molecular-weight metallohydrogel (ZAVA). Pristine ZAVA hydrogel shows blue luminescence, but the emission can be tuned upon encapsulation of the CdS quantum dots. Time-dependent tunable emission (white to yellow to orange) of the CdS incubated gel (CdS@ZAVA gel) can be attributed to sluggish growth of the quantum dots inside the gel matrix. Once CdS quantum dots are entrapped, their augmentation can be stopped by converting the gel into xerogel, wherein the quantum dots remains embedded in the solid xerogel matrix. Similar size stabilization of CdS quantum dots can be achieved by means of a unique room-temperature conversion of the CdS incubated ZAVA gel to CdS incubated MOF (CdS@ZAVCl) crystals. This in turn arrests the tunability in emission owing to the restriction in the growth of CdS quantum dots inside xerogel and MOF. These CdS embedded MOFs have been utilized as a catalyst for water splitting under visible light.

Photochromic metal organic frameworks for inkless and erasable printing - Garai, Bikash; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Erasable Printing; Inkless Printing; metal organic framework

Post modification of MOF derived carbon via g-C3N4 entrapment for an efficient metal-free oxygen reduction reaction - Pandiaraj, Sekar; Aiyappa, Harshitha Barike; Banerjee, Rahul; Kurungot, Sreekumar (Chemical Communications, 2014)
High surface area carbon with a nitrogen content of 7.0% is derived from MOF via in situ g-C3N4 formation. The material shows excellent ORR activity with an onset potential of 0.035 V (vs. Hg/HgO) in alkaline medium apart from high durability and strong disinclination towards methanol crossover.

Role of hydrogen bonding in pseudocapacitance of covalent organic frameworks - Chandra, Suman; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: COF; H-bonding; pseudocapacitance

Structural diversity in serine derived homochiral metal organic frameworks - Kundu, Tanay; Banerjee, Rahul (Journal of Chemical Sciences, 2014)
Two new Zn(II) and Cd(II) based homochiral metal-organic frameworks (MOFs) [SerCdOAc and Zn(Ser)(2)] have been synthesized using pyridyl functionalized amino acid, viz., serine, as an organic linker. The SerCdOAc structure is three dimensional, while that of the Zn(Ser)(2) is two dimensional. The polar voids of the corresponding MOFs are filled with solvent molecules (water in the case of SerCdOAc and methanol in the case of Zn(Ser)(2)). In both cases, metal centres, i.e., Zn(II) and Cd(II), are hexacoordinated. However, with a change in the solvent for synthesis, ligand coordination mode and incorporation of additional coordinated anion resulted in a great change in the final MOF architecture. Herein, for the first time, we could achieve structural variety and synthesize MOFs composed of only metal ion and pyridyl functionalized amino acid linker.
Keywords: Amino acid; crystal engineering; hydrogen bonding; metal organic framework

Sulfonic acid loaded self-standing covalent organic membrane for proton conduction - Sasmal, Himadri Sekhar; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: COF; Membrane; proton conduction

Supramolecular gel to metal organic framework transformation - Chakraborty, Amit; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: gel; MOF; Supramolecular

Tandem catalysis by in-situ generated microporous COF-Pd nanoparticle hybrids - Bhadra, Mohitosh; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: covalent organic frameworks; Pd nanoparticles; tandem catalysis

Variation of CO2 adsorption in isostructural Cd(II)/Co(II) based MOFs by anion modulation - Singh, Udai P.; Narang, Shikha; Pachfule, Pradip; Banerjee, Rahul (CrystEngComm, 2014)
{A potential multidentate tris-pyridyl ligand has been synthesized, and later employed for the tailoring of four isostructural cadmium(II)/cobalt(II) two dimensional (2D) metal organic frameworks, [[ M(dmpt)(2)(X)(2)].xS](n), where S = solvent

ZIF-8@PBI-Bul composite membranes: elegant effects of PBI structural variations on gas permeation performance - Bhaskar, Anand; Banerjee, Rahul; Kharul, Ulhas K. (Journal of Materials Chemistry A, 2014)
The composites of metal organic frameworks (MOFs) and polymers look promising as membrane materials for gas separation, provided benefits of both the components can be shown successfully. This work shows that the structural architecture of polybenzimidazole (PBI) is highly advantageous in offering attractive gas permeation properties of its composites with MOFs. PBI-Bul and its N-substituted (methyl and 4-tert-butylbenzyl) derivatives were blended with ZIF-8. In general, homogeneous blend formation of ZIF-8 was achieved with all three polymers, as supported by SEM. Wide angle X-ray diffraction, mechanical property analysis and density measurements of the composite membranes were performed in order to understand the effects of physical blending of MOFs and polymers. Gas permeability analysis of the composite membranes revealed that the properties of MOFs as well as those of polymers arising from their structural architecture are responsible for governing the permeability and selectivity of the resulting composites.

Bifunctional covalent organic frameworks with two dimensional organocatalytic micropores - Shinde, Digambar Balaji; Kandambeth, Sharath; Pachfule, Pradip; Kumar, Raya Rahul; Banerjee, Rahul (Chemical Communications, 2015)
We report the successful incorporation of bifunctional (acid/base) catalytic sites in the crystalline organocatalytic porous COF (2,3-DhaTph). Due to the presence of acidic (catachol) and basic (porphyrin) sites, 2,3-DhaTph shows significant selectivity, reusability, and excellent ability to perform the cascade reaction.

Chemical sensing in two dimensional porous covalent organic nanosheets - Das, Gobinda; Biswal, Bishnu P.; Kandambeth, Sharath; Venkatesh, V.; Kaur, Gagandeep; Addicoat, Matthew A.; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul (Chemical Science, 2015)
Two new imide-based crystalline, porous, and chemically stable covalent organic frameworks (COFs) (TpBDH and TfpBDH) have been successfully synthesized employing solvothermal crystallization route. Furthermore, thin layered covalent organic nanosheets (CONs) were derived from these bulk COFs by the simple liquid phase exfoliation method. These 2D CONs showcase increased luminescence intensity compared to their bulk counterparts (COFs). Notably, TfpBDH-CONs showcase good selectivity and prominent, direct visual detection towards different nitroaromatic analytes over TpBDH-CONs. Quite interestingly, TfpBDH-CONs exhibit a superior ``turn-on'' detection capability for 2,4,6-trinitrophenol (TNP) in the solid state, but conversely, they also show a ``turn-off'' detection in the dispersion state. These findings describe a new approach towards developing an efficient, promising fluorescence chemosensor material for both visual and spectroscopic detection of nitroaromatic compounds with very low [10(-5) (M)] analyte concentrations.

Fe(III) phytate metallogel as a prototype anhydrous, intermediate temperature proton conductor - Aiyappa, Harshitha Barike; Saha, Subhadeep; Wadge, Pritish; Banerjee, Rahul; Kurungot, Sreekumar (Chemical Science, 2015)
A proton conducting metallogel [FNPA; ferric nitrate (FN)-phytic acid (PA)] is synthesized by immobilizing a protogenic ligand (phytic acid) using iron(III) nitrate in DMF. The xerogel shows high proton conductivity of 2.4 x 10(-2) S cm(-1) at 120 degrees C, the best value known among all metal organic materials (MOMs). Marking the first such attempt in MOMs, an electrode made using the xerogel showed a power density of 0.94 mW cm(-2) at 0.6 V under dry fuel cell conditions.

Gelation landscape engineering using a multi-reaction supramolecular hydrogelator system - Foster, Jamie S.; Zurek, Justyna M.; Almeida, Nuno M. S.; Hendriksen, Wouter E.; le Sage, Vincent A. A.; Lakshminarayanan, Vasudevan; Thompson, Amber L.; Banerjee, Rahul; Eelkema, Rienk; Mulvana, Helen; Paterson, Martin J.; van Esch, Jan H.; et al. (Journal of the American Chemical Society, 2015)
Simultaneous control of the kinetics and thermodynamics of two different types of covalent chemistry allows pathway selectivity in the formation of hydrogelating molecules from a complex reaction network. This can lead to a range of hydrogel materials with vastly different properties, starting from a set of simple starting compounds and reaction conditions. Chemical reaction between a trialdehyde and the tuberculosis drug isoniazid can form one, two, or three hydrazone connectivity products, meaning kinetic gelation pathways can be addressed. Simultaneously, thermodynamics control the formation of either a keto or an enol tautomer of the products, again resulting in vastly different materials. Overall, this shows that careful navigation of a reaction landscape using both kinetic and thermodynamic selectivity can be used to control material selection from a complex reaction network.

Hollow tubular porous covalent organic framework (COF) nanostructures - Pachfule, Pradip; Kandmabeth, Sharath; Mallick, Arijit; Banerjee, Rahul (Chemical Communications, 2015)
Hollow and tubular TpPa-COF structures have been synthesized by template-assisted replication of nanometer sized ZnO-nanorods. The hollow structures composed of microporous TpPa shells have high periodicity, moderate porosity, chemical stability and capsule shaped morphology as revealed by X-ray diffraction, porosity measurements, and SEM and TEM analyses.

One-dimensional water cages with repeat units of (H2O)(24) resembling pagodane trapped in a 3D coordination polymer: proton conduction and tunable luminescence emission by adsorption of anionic dyes - Maity, Kartik; Kundu, Tanay; Banerjee, Rahul; Biradha, Kumar (Crystengcomm, 2015)
A 3D-coordination polymer was shown to trap one-dimensional polyhedral water cages consisting of repeat units of (H2O)(24), the geometry of which resembles the exotic organic molecule pagodane. Further, this material exhibited proton conduction ability and tunable luminescence emission by adsorption of anionic dyes such as the fluorescein dianion.

Phosphate enriched polyoxometalate based ionic salts for proton conduction - Dey, Chandan; Kundu, Tanay; Aiyappa, Harshitha Barike; Banerjee, Rahul (RSC Advances, 2015)
A series of [NiMo12O30(PO4)(8)](n-) POM anion and organic cation based ionic composites have been prepared in hydrothermal conditions. The ionic composites with protonated ethylene diamine molecules have been tested for proton conductivity.

Pore surface engineering in porous, chemically stable covalent organic frameworks for water adsorption - Biswal, Bishnu P.; Kandambeth, Sharath; Chandra, Suman; Shinde, Digambar Balaji; Bera, Saibal; Karak, Suvendu; Garai, Bikash; Kharul, Ulhas K.; Banerjee, Rahul (Journal of Materials Chemistry A, 2015)
Herein, we have explored the possibility of a class of covalent organic frameworks (COFs) as water adsorbing materials. We have selected, synthesized 12 chemically stable functionalized Schiff base COFs and thoroughly studied their water uptake behaviour. Further, a deep understanding was developed with these COFs towards the effects of condensation pressure of water and hydrophilic/hydrophobic groups present in the COF pores on water absorption capacity and ultimately, their recyclability. Among all reported COFs, TpPa-1 shows the highest water uptake of 30 wt% (368 cm(3) g(-1); 17 mmol g(-1)) at P/P-0 = 0.3, which is also comparable with the recently reported carbon materials and few well known MOFs. This study also reveals that the overall water uptake of COFs can be tuned systematically based on chemical functionality and pore size in a wider window of relative pressures.

Selective interfacial synthesis of metal-organic frameworks on a polybenzimidazole hollow fiber membrane for gas separation - Biswal, Bishnu P.; Bhaskar, Anand; Banerjee, Rahul; Kharul, Ulhas K. (Nanoscale, 2015)
Metal-organic frameworks (MOFs) have gained immense attention as new age materials due to their tuneable properties and diverse applicability. However, efforts on developing promising materials for membrane based gas separation, and control over the crystal growth positions on polymeric hollow fiber membranes still remain key challenges. In this investigation, a new, convenient and scalable room temperature interfacial method for growing MOFs (ZIF-8 and CuBTC) on either the outer or inner side of a polybenzimidazole based hollow fiber (PBI-BuI-HF) membrane surface has been achieved in a controlled manner. This was made possible by the appropriate selection of an immiscible solvent pair and the synthetic conditions. The growth of MOFs on the PBI-BuI-HF membrane by the interfacial method was continuous and showed an appreciable gas separation performance, conveying promise for their applicability.

Self-templated chemically stable hollow spherical covalent organic framework - Kandambeth, Sharath; Venkatesh, V.; Shinde, Digambar B.; Kumari, Sushma; Halder, Arjun; Verma, Sandeep; Banerjee, Rahul (Nature Communications, 2015)
Covalent organic frameworks are a family of crystalline porous materials with promising applications. Although active research on the design and synthesis of covalent organic frameworks has been ongoing for almost a decade, the mechanisms of formation of covalent organic frameworks crystallites remain poorly understood. Here we report the synthesis of a hollow spherical covalent organic framework with mesoporous walls in a single-step template-free method. A detailed time-dependent study of hollow sphere formation reveals that an inside-out Ostwald ripening process is responsible for the hollow sphere formation. The synthesized covalent organic framework hollow spheres are highly porous (surface area similar to 1,500m(2) g(-1)), crystalline and chemically stable, due to the presence of strong intramolecular hydrogen bonding. These mesoporous hollow sphere covalent organic frameworks are used for a trypsin immobilization study, which shows an uptake of 15.5 mu mol g(-1) of trypsin.

Single crystal-to-single crystal site-selective postsynthetic metal exchange in a Zn-MOF based on semi-rigid tricarboxylic acid and access to bimetallic MOFs - Bajpai, Alankriti; Chandrasekhar, Pujari; Govardhan, Savitha; Banerjee, Rahul; Moorthy, Jarugu Narasimha (Chemistry-A European Journal, 2015)
The metal ions in a neutral Zn-MOF constructed from tritopic triacid H3L with inherent concave features, rigid core, and peripheral flexibility are found to exist in two distinct SBUs, that is, 0D and 1D. This has allowed site-selective postsynthetic metal exchange (PSME) to be investigated and reactivities of the metal ions in two different environments in coordination polymers to be contrasted for the first time. Site-selective transmetalation of Zn ions in the discrete environment is shown to occur in a single crystal-to-single crystal (SCSC) fashion, with metal ions such as Fe3+, Ru3+, Cu2+, Co2+, etc., whereas those that are part of 1D SBU sustain structural integrity, leading to novel bimetallic MOFs, which are inaccessible by conventional approaches. To the best of our knowledge, site-selective postsynthetic exchange of an intraframework metal ion in a MOF that contains metal ions in discrete as well as polymeric SBUs is heretofore unprecedented.
Keywords: coordination polymers; metal-exchange; metal-organic frameworks; Metathesis; X-ray crystallography

Solid state organic amine detection in a photochromic porous metal organic framework - Mallick, Arijit; Garai, Bikash; Addicoat, Matthew A.; Petkov, Petko St.; Heine, Thomas; Banerjee, Rahul (Chemical Science, 2015)
A new Mg(II) based photochromic porous metal-organic framework (MOF) has been synthesized bearing naphthalenediimide (NDI) chromophoric unit. This MOF (Mg-NDI) shows instant and reversible solvatochromic behavior in presence of solvents with different polarity. Mg-NDI also exhibits fast and reversible photochromism via radical formation. Due to the presence of electron deficient NDI moiety, this MOF exhibits selective organic amine (electron rich) sensing in solid state. The organic amine detection has been confirmed by photoluminescence quenching experiment and visual color change.

2016 New talent: crystal engineering at its biggest and strongest - Banerjee, Rahul; Day, Graeme M.; Friscic, Tomislav; Zhang, Hongjie (Crystengcomm, 2016)

Chemically delaminated free-standing ultrathin covalent organic nanosheets - Khayum, M. Abdul; Kandambeth, Sharath; Mitra, Shouvik; Nair, Sanoop B.; Das, Anuja; Nagane, Samadhan S.; Mukherjee, Rabibrata; Banerjee, Rahul (Angewandte Chemie-International Edition, 2016)
Covalent organic nanosheets (CONs) are a new class of porous thin two-dimensional (2D) nanostructures that can be easily designed and functionalized and could be useful for separation applications. Poor dispersion, layer restacking, and difficult postsynthetic modifications are the major hurdles that need to be overcome to fabricate scalable CON thin films. Herein, we present a unique approach for the chemical exfoliation of an anthracene-based covalent organic framework (COF) to N-hexylmaleimide-functionalized CONs, to yield centimeter-sized free-standing thin films through layer-by-layer CON assembly at the air-water interface. The thinlayer fabrication technique presented here is simple, scalable, and does not require any surfactants or stabilizing agents.

Chemically stable covalent organic framework (COF)-polybenzimidazole hybrid membranes: enhanced gas separation through pore modulation - Biswal, Bishnu P.; Chaudhari, Harshal D.; Banerjee, Rahul; Kharul, Ulhas K. (Chemistry-A European Journal, 2016)
Highly flexible, TpPa-1@PBI-BuI and TpBD@PBI-BuI hybrid membranes based on chemically stable covalent organic frameworks (COFs) could be obtained with the polymer. The loading obtained was substantially higher (50%) than generally observed with MOFs. These hybrid membranes show an exciting enhancement in permeability (about sevenfold) with appreciable separation factors for CO2/N-2 and CO2/CH4. Further, we found that with COF pore modulation, the gas permeability can be systematically enhanced.
Keywords: covalent organic frameworks; Gas separation; membranes; microporous materials; pore modulation

Cobalt-modified covalent organic framework as a robust wateroxidation electrocatalyst - Aiyappa, Harshitha Barike; Thote, Jayshri; Shinde, Digambar Balaji; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry of Materials, 2016)
The development of stable, efficient oxygen evolution reaction (OER) catalyst capable of oxidizing water is one of the premier challenges in the conversion of solar energy to electrical energy, because of its poor kinetics. Herein, a bipyridine-containing covalent organic framework (TpBpy) is utilized as an OER catalyst by way of engineering active Co(II) ions into its porous framework. The as-obtained Co-TpBpy retains a highly accessible surface area (450 m(2)/g) with exceptional stability, even after 1000 cycles and 24 h of OER activity in phosphate buffer under neutral pH conditions with an overpotential of 400 mV at a current density of 1 mA/cm(2). The unusual catalytic stability of Co-TpBpy arises from the synergetic effect of the inherent porosity and presence of coordinating units in the COF skeleton.

Constructing covalent organic frameworks in water via dynamic covalent bonding - Thote, Jayshri; Aiyappa, Harshitha Barike; Kumar, Raya Rahul; Kandambeth, Sharath; Biswal, Bishnu P.; Shinde, Digambar Balaji; Roy, Neha Chaki; Banerjee, Rahul (Iucrj, 2016)
The formation of keto-enamine based crystalline, porous polymers in water is investigated for the first time. Facile access to the Schiff base reaction in water has been exploited to synthesize stable porous structures using the principles of Dynamic Covalent Chemistry (DCC). Most credibly, the water-based Covalent Organic Frameworks (COFs) possess chemical as well as physical properties such as crystallinity, surface area and porosity, which is comparable to their solvothermal counterparts. The formation of COFs in water is further investigated by understanding the nature of the monomers formed using hydroxy and non-hydroxy analogues of the aldehyde. This synthetic route paves a new way to synthesize COFs using a viable, greener route by utilization of the DCC principles in conjunction with the keto-enol tautomerism to synthesize useful, stable and porous COFs in water.

Decoding the morphological diversity in two dimensional crystalline porous polymers by core planarity modulation - Halder, Arjun; Kandambeth, Sharath; Biswal, Bishnu P.; Kaur, Gagandeep; Roy, Neha Chaki; Addicoat, Matthew A.; Salunke, Jagadish K.; Banerjee, Subhrashis; Vanka, Kumar; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul (Angewandte Chemie - International Edition, 2016)

Functionalization and isoreticulation in a series of metal-organic frameworks derived from pyridinecarboxylates - Pachfule, Pradip; Garai, Bikash; Banerjee, Rahul (Inorganic Chemistry, 2016)
The partially fluorinated metal-organic frameworks (F-MOFs) have been constructed from 3-fltoro-4-pyridinecarboxylic acid and trans-3-fluoro-4-pyridineacrylic acid linkers using Mn2+, Co2+, and, Cd2+ metals via the solvothetrnal method, which show isostructural isomerism with their nonfluorinated counterparts synthesized using 4-pyridinecarboxylic acid and trans-4-pyridineacrylic acid, respectively. The simultaneous effect of partial fluorination and isoreticulation on structure and H-2 adsorption has been studied systematically in isostructural nonfluorinated and partially fluorinated MOFs, which shows that the increment in the hydrogen uptake properties in F-MOFs is not a universal phenomenon but is rather system-specific and changes from one system to another.

Gadolinium(III)-based porous luminescent metal-organic frameworks for bimodal imaging - Kundu, Tanay; Mitra, Shouvik; Diaz Diaz, David; Banerjee, Rahul (Chempluschem, 2016)
Gd-III-based metal-organic frameworks, Gd-pDBI-1 and Gd-pDBI-2, have been synthesized using the linker pDBI (pDBI=1,4-bis(5-carboxy-1H-benzimidazole-2yl)benzene). They exhibited structural diversity due to subtle change in reaction constituents. Owing to the judicious choice of the fluorescent linker, the materials could be used for bimodal imaging (fluorescent and magnetic resonance) and displayed a modest T1 relaxivity value.

High loading of pd nanoparticles by interior functionalization of mofs for heterogeneous catalysis - Gole, Bappaditya; Sanyal, Udishnu; Banerjee, Rahul; Mukherjee, Partha Sarathi (Inorganic Chemistry, 2016)
In this report, the issue related to nanoparticle (NP) agglomeration upon increasing their loading amount into metal-organic frameworks (MOFs) has been addressed by functionalization of MOFs with alkyne groups. The alkynophilicity of the Pd2+ (or other noble metals) ions has been utilized successfully for significant loading of Pd NPs into alkyne functionalized MOFs. It has been shown here that the size and loading amount of Pd NPs are highly dependent on the surface area and pore width of the MOFs. The loading amount of Pd NPs was increased monotonically without altering their size distribution on a particular MOF. Importantly, the distinct role of alkyne groups for Pe(2+) stabilization has also been demonstrated by performing a control experiment considering a MOF without an alkyne moiety. The preparation of NPs involved two distinct steps viz. adsorption of metal ions inside MOFs and reduction of metal ions. Both of these steps were monitored by microscopic techniques. This report also demonstrates the applicability of Pd@MOF NPs as extremely efficient heterogeneous catalysts for Heck-coupling and hydrogenation reactions of aryl bromides or iodides and alkenes, respectively.

Interplaying intrinsic and extrinsic proton conductivities in covalent organic frameworks - Chandra, Suman; Kundu, Tanay; Dey, Kaushik; Addicoat, Matthew A.; Heine, Thomas; Banerjee, Rahul (Chemistry of Materials, 2016)
A sulfonic-acid-based covalent organic framework (TpPa-SO3H) has been synthesized that exhibits intrinsic proton conductivity under anhydrous conditions. The sulfonic acid groups are aligned on the two-dimensional (2D) layers at periodic intervals and promote the proton hopping inside the hexagonal one-dimensional channel. The intrinsic proton conductivity of TpPa-SO3H was measured as 1.7 X 10(-5) S cm(-1) at 120 degrees C under anhydrous conditions. To enhance the proton conductivity, we have synthesized a hybrid COF TpPa(SO3H-Py) by a ligand-based solid-solution approach that contains sulfonic acid as the acidic site, as well as pyridine as the basic site, in order to immobilize acidic proton carrier molecules. Impregnation of phytic acid molecules inside the framework increases the anhydrous proton conductivity up to 5 x 10(-4) S cm(-1) at 120 degrees C. Such an approach highlights the advantage and first-time use of hybrid COF for interplaying intrinsic to extrinsic proton conductivity.

Mechanochemically synthesized covalent organic framework as a proton-conducting solid electrolyte - Shinde, Digambar Balaji; Aiyappa, Harshitha Barike; Bhadra, Mohitosh; Biswal, Bishnu P.; Wadge, Pritish; Kandambeth, Sharath; Garai, Bikash; Kundu, Tanay; Kurungot, Sreekumar; Banerjee, Rahul (Journal of Materials Chemistry A, 2016)
Mechanochemistry has become an increasingly important synthetic tool for a waste-free environment. However, the poor quality of the so-derived materials in terms of their crystallinity and porosity has been their major drawback for any practical applications. In this report, we have for the first time successfully leveraged such characteristics to show that the mechanochemically synthesized bipyridine based covalent organic framework (COF) outperforms its conventional solvothermal counterpart as an efficient solid-state electrolyte in PEM fuel cells. Marking the first such attempt in COFs, a Membrane Electrode Assembly (MEA) fabricated using the mechanochemically synthesized COF was observed to inhibit the fuel crossover and build up a stable Open Circuit Voltage (OCV = 0.93 V at 50 degrees C), thereby establishing itself as an effective solid electrolyte material (with a proton conductivity of 1.4 x 10(-2) S cm(-1)), while the solvothermally synthesized COF proved ineffective under similar conditions.

Photochromic metal-organic frameworks for inkless and erasable printing - Garai, Bikash; Mallick, Arijit; Banerjee, Rahul (Chemical Science, 2016)
Inkless and erasable printing is the key solution towards a more sustainable paper industry, in terms of reducing paper wastages and the associated environmental hazards from waste paper processing. However, only a few cases have been reported in the literature where inkless printing has been tested in some practical systems. In an attempt to address this solution, we used photochromic metal-organic frameworks (MOFs) and tested their capability as inkless and erasable printing media. The printing was performed using sunlight as the light source on MOF-coated papers. The resulting printing had good resolution and stability, and was capable of being read both by the human eye and smart electronic devices; furthermore, the paper could be reused for several cycles without any significant loss in intensity. Interestingly, different coloured printing with a similar efficiency was achieved by varying the structure of the MOF.

Self-exfoliated metal-organic nanosheets through hydrolytic unfolding of metal-organic polyhedra - Garai, Bikash; Mallick, Arijit; Das, Anuja; Mukherjee, Rabibrata; Banerjee, Rahul (Chemistry-A European Journal, 2016)
Few-layers thick metal-organic nanosheets have been synthesized using water-assisted solid-state transformation through a combined top-down and bottom-up approach. The metal-organic polyhedra (MOPs) convert into metal-organic frameworks (MOFs) which subsequently selfexfoliate into few-layered metal-organic nanosheets. These MOP crystals experience a hydrophobicity gradient with the inner surface during contact with water because of the existence of hydrophobic spikes on their outer surface. When the amount of water available for interaction is higher, the resultant layers are not stacked to form bulk materials; instead few-layered nanosheets with high uniformity were obtained in high yield. The phenomenon has resulted high yield production of uniformly distributed layered metal-organic nanosheets from three different MOPs, showing its general adaptability.

State-of-the-art catechol porphyrin COF catalyst for chemical fixation of carbon dioxide via cyclic carbonates and oxazolidinones - Saptal, Vitthal; Shinde, Digambar Balaji; Banerjee, Rahul; Bhanage, Bhalchandra M. (Catalysis Science & Technology, 2016)
A highly porous, crystalline catechol porphyrin COF was synthesized and applied as an organocatalyst for the chemical fixation of carbon dioxide to synthesize value-added chemicals such as cyclic carbonates and oxazolidinones under solvent-free and transition-metal-free conditions. The high surface area and the functionalities of the COF catalyst act synergistically to activate the starting material. The 2,3-DhaTph shows excellent activity towards cyclic carbonates at the atmospheric pressure of carbon dioxide. Additionally, this catalytic system is recyclable in nature and provides a higher turnover number than previously reported organocatalysts.

Supramolecular metallogel that imparts self-healing properties to other gel networks - Feldner, Tobias; Haering, Marleen; Saha, Subhadeep; Esquena, Jordi; Banerjee, Rahul; Diaz, David Diaz (Chemistry of Materials, 2016)
A unique proton conductive and moldable supramolecular metallogel (CuA-Ox-gel) made upon mixing at room temperature well-defined stock solutions of Cu(OAc)(2). H2O and oxalic acid dehydrate was found to have self-healing properties. Remarkably, the system also displayed an unprecedented ability to impart self-healing properties to other gel networks lacking this capacity. A self-healed CuA-Ox metallogel was found to have essentially the same nanofibrillar morphology, thermal stability, rheological properties, and conductivity as the freshly prepared sample. The discovery also allowed the fabrication of self-healing conductive composites containing conductive carbonaceous materials. Overall, this work serves as a proof of concept for the transfer of self-healing properties between completely different gel networks.

Covalent organic frameworks and organic cage structures - Banerjee, Rahul; Champness, Neil R. (CrystEngComm, 2017)

Interplaying anions in a supramolecular metallohydrogel to form metal organic frameworks - Karak, Suvendu; Kumar, Sushil; Bera, Saibal; Diaz Diaz, David; Banerjee, Subhrashis; Vanka, Kumar; Banerjee, Rahul (Chemical Communications, 2017)
The remarkable effect of anions on the transition from supramolecular gels to crystalline phases has been described. An amino acid-based metallohydrogel was transformed into different metal-organic frameworks through the selective picking of anions. The metallohydrogel and the resulting metal-organic frameworks (MOFs) were thoroughly characterized. The results demonstrated controlled access over the binding of a particular anion to selectively form a particular MOF.

Porous porphyrin organic polymer (PPOP) for visible light triggered hydrogen production - Mukherjee, Gargi; Thote, Jayshri; Aiyappa, Harshitha Barike; Kandambeth, Sharath; Banerjee, Subhrashis; Vanka, Kumar; Banerjee, Rahul (Chemical Communications, 2017)
A visible light active porphyrin-based porous organic polymer having high chemical stability and surface area has been synthesized and its ability to influence the photocatalytic activity of large band gap-TiO2 nanoparticles has been tested. The resultant composite shows improved photocatalytic activity as compared to the parent precursors. This study provides insights into the photosensitizing ability of the polymer in addition to its ability to firmly harbor nanoparticles onto its surface.

Predesigned metal-anchored building block for in situ generation of Pd nanoparticles in porous covalent organic framework: application in heterogeneous tandem catalysis - Bhadra, Mohitosh; Sasmal, Himadri Sekhar; Basu, Arghya; Midya, Siba P.; Kandambeth, Sharath; Pachfule, Pradip; Balaraman, Ekambaram; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2017)
The development of nanoparticle-polymer-hybrid-based heterogeneous catalysts with high reactivity and good recyclability is highly desired for their applications in the chemical and pharmaceutical industries: Herein, we have developed a novel synthetic strategy by choosing a predesigned metal-anchored building block for in situ generation of metal (Pd) nanoparticles in the stable, porous, and crystalline covalent organic framework (COF), without using conventional reducing agents. In situ generation of Pd nanoparticles in the COF Skeleton is explicitly confirmed' from PXRD, XPS, TEM images, and N-15 NMR spectral analysis. This hybrid material is found to be an excellent reusable heterogeneous catalyst for the synthesis of biologically and pharmaceutically important 2-substituted benzofurans from 2-bromophencils and terminal alkynes via a tandem process with the turnover number up to 1101. The heterogeneity of the catalytic process is unambiguously verified by a mercury poisoning experiment and leaching test. This hybrid material shows superior catalytic performance compared to commercially available homogeneous as well as heterogeneous Pd catalysts.

Self-exfoliated guanidinium-based ionic covalent organic nanosheets (iCONs) - Mitra, Shouvik; Kandambeth, Sharath; Biswal, Bishnu P.; Khayum, Abdul M.; Choudhury, Chandan Kumar; Mehta, Mihir R.; Kaur, Gagandeep; Banerjee, Subhrashis; Prabhune, Asmita; Verma, Sandeep; Roy, Sudip; Kharul, Ulhas K.; et al. (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as functional two-dimensional materials for versatile applications. Although pi-pi stacking between layers, hydrolytic instability, possible restacking prevents their exfoliation on to few thin layered CONs from crystalline porous polymers. We anticipated rational designing of a structure by intrinsic ionic linker could be the solution to produce self-exfoliated CONs without external stimuli. In an attempt to address this issue, we have synthesized three self-exfoliated guanidinium halide based ionic covalent organic nanosheets (iCONs) with antimicrobial property. Self-exfoliation phenomenon has been supported by molecular dynamics (MD) simulation as well. Intrinsic ionic guanidinium unit plays the pivotal role for both self-exfoliation and antibacterial property against both Gram-positive and Gram-negative bacteria. Using such iCONs, we have devised a Mixed matrix membrane which could be useful for antimicrobial coatings with plausible medical benefits.

Synthesis, characterization and electrochemical investigations of mixed-ligand copper(II)-organic supramolecular frameworks - Singh, Sandeep K.; Srivastava, Ashish Kumar; Srivastava, Krishna; Banerjee, Rahul; Prasad, Jagdish (Journal of Molecular Structure, 2017)
Two mixed-ligand copper(II)-organic coordination compounds with 5,5'-dimethyl-2,2'-bipyridine (5,5'-Me(2)bpy) as a primary ligand while aliphatic malonate (Hmal) and aromatic 2-hydroxynicotinate (2-OHNA) as secondary ligands, were synthesized. These complexes are formulated as: [Cu(Hmal)(5,5'-Me(2)bPY)(H2O)](ClO4) 1 and [Cu-2(2-OHNA)(2)(5,5'-Me(2)bpy)(2)(NO3)KNO3) 2. These two complexes were structurally characterized by single crystal X-ray diffraction analysis. Characterization was further supported by powder X-ray diffraction analysis, elemental analyses, FT-IR, FAB-MASS and TGA, DSC studies. Cyclic voltammetric and UV-visible spectral studies of these two complexes have also been done. The electrochemical studies of complex 1 in DMSO and DMF have shown that this complex undergoes quasi reversible diffusion-controlled one-electron transfer reaction without any chemical complication while complex 2 in DMSO undergoes quasi-reversible diffusion-controlled one electron transfer reaction, following EC mechanism. The electrochemical behaviour of complex 2 in DMF is complicated probably due to presence of more than one species in solution phase. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: 2 '-bipyridine; 3; 5; 5 '-dimethyl-2; 5-Tricarboxylic acid; Benzene-1; classification; Co-ordination-Compounds; Crystal-structures; cyclic voltammetry; magnetic properties; metal organic framework; Mixed-ligand complex; pi-pi stacking interaction; Polymers; Secondery Building Unit; Structural data; Supramolecular framework; Ternare Komplexe; X-ray diffraction

Targeted drug delivery in covalent organic nanosheets (CONs) via sequential postsynthetic modification - Mitra, Shouvik; Sasmal, Himadri Sekhar; Kundu, Tanay; Kandambeth, Sharath; Math, Kavya; Diaz Diaz, David; Banerjee, Rahul (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as a new class of functional two-dimensional (2D) porous organic polymeric materials with a high accessible surface, diverse functionality, and chemical stability. They could become versatile candidates for targeted drug delivery. Despite their many advantages, there are limitations to their use for target specific drug delivery. We anticipated that these drawbacks could be overturned by judicious postsynthetic modification steps to use CONs for targeted drug delivery. The postsynthetic modification would not only produce the desired functionality, it would also help to exfoliate to CONs as well. In order to meet this requirement, we have developed a facile, salt-mediated synthesis of covalent organic frameworks (COFs) in the presence of p-toluenesulfonic acid (PTSA). The COFs were subjected to sequential postsynthetic modifications to yield functionalized targeted CONs for targeted delivery of 5-fluorouracil to breast cancer cells. This postsynthetic modification resulted in simultaneous chemical delamination and functionalization to targeted CONs. Targeted CONs showed sustained release of the drug to the cancer cells through receptor mediated endocytosis, which led to cancer cell death via apoptosis. Considering the easy and facile COF synthesis, functionality based postsynthetic modifications, and chemical delamination to CONs for potential advantageous targeted drug delivery, this process can have a significant impact in biomedical applications.

Convergent covalent organic framework thin sheets as flexible supercapacitor electrodes - Khayum, Abdul M.; Vijayakumar, Vidyanand; Karak, Suvendu; Kandambeth, Sharath; Bhadra, Mohitosh; Suresh, Karthika; Acharambath, Nikhil; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Material & Interfaces, 2018)
Flexible supercapacitors in modern electronic equipment require light-weight electrodes, which have a high surface area, precisely integrated redox moieties, and mechanically strong flexible free-standing nature. However, the incorporation of the aforementioned properties into a single electrode remains a great task. Herein, we could overcome these challenges by a facile and scalable synthesis of the convergent covalent organic framework (COF) free-standing flexible thin sheets through solid-state molecular baking strategy. Here, redox-active anthraquinone (Dq) and pi-electron-rich anthracene (Da) are judiciously selected as two different linkers in a beta-ketoenamine-linked two-dimensional (2D) COF. As a result of precisely integrated anthraquinone moieties, COF thin sheet exhibits redox activity. Meanwhile, pi-electron-rich anthracene linker assists to improve the mechanical property of the free-standing thin sheet through the enhancement of noncovalent interaction between crystallites. This binder-free strategy offers the togetherness of crystallinity and flexibility in 2D COF thin sheets. Also, the synthesized porous crystalline convergent COF thin sheets are benefited with crack-free uniform surface and light-weight nature. Further, to demonstrate the practical utility of the material as an electrode in energy-storage systems, we fabricated a solid-state symmetrical flexible COF supercapacitor device using a GRAFOIL peeled carbon tape as the current collector.

Interlayer hydrogen-bonded covalent organic frameworks as high-performance supercapacitors - Halder, Arjun; Ghosh, Meena; Khayum, Abdul M.; Bera, Saibal; Addicoat, Matthew; Sasmal, Himadri Sekhar; Karak, Suvendu; Kurungot, Sreekumar; Banerjee, Rahul (Journal of the American Chemical Society, 2018)
Covalent organic frameworks (COFs) have emerged as promising electrode materials in supercapacitors (SCs). However, their insoluble powder-like nature, poor capacitive performance in pristine form, integrated with inferior electrochemical stability is a primary concern for their long-term use in electrochemical devices. Keeping this in perspective, herein we report a redox active and hydrogen bonded COF with ultrahigh stability in conc. H2SO4 (18 M), conc. HCl (12 M) and NaOH (9 M). The as-synthesized COF fabricated as thin sheets were efficiently employed as a free-standing supercapacitor electrode material using 3 M aq. H2SO4 as an electrolyte. Moreover, the pristine COF sheet showcased outstanding areal capacitance 1600 mF cm(-2) (gravimetric 169 F g(-1)) and excellent cyclic stability (>100 000) without compromising its capacitive performance or Coulombic efficiency. Moreover, as a proof-of-concept, a solid-state supercapacitor device was also assembled and subsequently tested.

Multistimuli-responsive interconvertible low-molecular weight metallohydrogels and the in situ entrapment of CdS quantum dots therein - Bera, Saibal; Chakraborty, Amit; Karak, Suvendu; Halder, Arjun; Chatterjee, Soumyajyoti; Saha, Subhadeep; Banerjee, Rahul (Chemistry of Materials, 2018)
Two low molecular weight metallohydrogels (ZALA and CALA) have been synthesized from an amino-acid based ligand precursor (LA) and two different metal salts [zinc acetate dihydrate (ZA) and cadmium acetate dihydrate (CA), respectively. These two hydrogels show a unique chemically stimulated interconversion to each other via a reversible gel-sol gel pathway. This programmable gel-sol reversible system satisfies logic operations of a basic Boolean logic (INHIBIT) gate. Also, these hydrogels can be degraded into different MOF phases at room temperature spontaneously or in the presence of chloride and bromide salts (NaCl and NaBr.). CdS quantum dots can be grown inside the CALA gel matrix (CdS@CALA) in the presence of small amount of Na2S. This CdS doped gel exhibits time dependent tunable emission (white to yellow to orange) as a consequence of a slow agglomeration process of the entrapped quantum dots inside the gel matrix. This luminescence property also reflects the corresponding gel derived MOFs (obtained either by self-degradation of CdS@CALA or via anion induction) as well. This, to the best of our knowledge, is probably the simplest way to make a CdS quantum dot based composite material where CdS is entrapped within the gel and the gel-derived MOF matrix.

Porosity prediction through hydrogen bonding in covalent organic frameworks - Karak, Suvendu; Kumar, Sushil; Pachfule, Pradip; Banerjee, Rahul (Journal of the American Chemical Society, 2018)
Easy and bulk-scale syntheses of two-dimensional (2D) covalent organic frameworks (COFs) represent an enduring challenge in material science. Concomitantly, the most critical aspect is to precisely control the porosity and crystallinity of these robust structures. Disparate complementary approaches such as solvothermal synthesis have emerged recently and are fueled in part by the usage of different modulators and acids that have enriched the COF library. Yet, the fundamental understanding of the integral processes of 2D COF assembly, induding their growth from nucleating sites and the origin of periodicity, is an intriguing chemical question that needs to be answered. To address these cardinal questions, a green and easy-to-perform approach of COF formation has been delineated involving acid-diamine salt precursors. The role of hydrogen bonding [d(av)(N-amine-H center dot center dot center dot O-acid); d(av) signifies the average N-amine-H center dot center dot center dot O-acid distances, i.e., the average distance from the H atom of the amine to the O atom of the acid] present in the acid-diamine salts in improving the COFs' crystallinity and porosity has further been decoded by thorough crystallographic analyses of the salt molecules. What is particularly noteworthy is that we have established the hydrogen-bonding distances d(av)(N-amine-H center dot center dot center dot O-acid) in the acid-diamine salts that are pivotal in maintaining the reversibility of the reaction, which mainly facilitates highly crystalline and porous COF formation. Moreover, this reactant-structure to the product-quality relationship has further been utilized for the synthesis of highly crystalline and porous COFs that are unattainable by other synthetic means.

Superprotonic conductivity in flexible porous covalent organic framework membranes - Banerjee, Rahul; Sasmal, Himadri Sekhar; Harshitha, B. A.; Bhange, Siddheshwar; Karak, Suvendu; Halder, Arjun; Kurungot, Sreekumar (Angewandte Chemie, 2018)
Poor mechanical stability of the polymer electrolyte membranes (PEMs) remains one of the bottlenecks towards improving the performance of the proton exchange membrane (PEM) fuel cells. The present work proposes a unique way to utilize crystalline covalent organic frameworks (COFs) as a self‐standing, highly flexible membrane to further boost the mechanical stability of the material without compromising its innate structural characteristics. The as‐synthesized p‐toluene sulfonic acid loaded covalent organic framework membranes (COFMs) showing the highest proton conductivity amongst all crystalline porous organic polymeric materials reported till date, as high as 7.8 x 10‐2 S cm‐1, have been further tested under real PEM operating conditions to ascertain their practical utilization as proton exchange membranes. Attainment of 24 mW cm‐2 power density, which is the highest among COFs and MOFs, highlights the possibilityof using a COF membrane over the other state‐of‐the‐art crystalline porous polymeric materials reported to date.

Supramolecular reassembly of self-exfoliated ionic covalent organic nanosheets for label-free detection of double-stranded DNA - Mal, Arindam; Mishra, Rakesh K.; Praveen, Vakayil K.; Khayum, M. Abdul; Banerjee, Rahul; Ajayaghosh, Ayyappanpillai (Angewandte Chemie-International Edition, 2018)
Ionic covalent organic nanosheets (iCONs), a member of the two-dimensional (2D) nanomaterials family, offer a unique functional platform for a wide range of applications. Herein, we explore the potential of an ethidium bromide (EB)-based covalent organic framework (EB-TFP) that self-exfoliates in water resulting in 2D ionic covalent organic nanosheets (EB-TFP-iCONs) for the selective detection of double-stranded DNA (dsDNA). In an aqueous medium, the self-exfoliated EB-TFP-iCONs reassemble in the presence of dsDNA resulting in hybrid EB-TFP-iCONs-DNA crystalline nanosheets with enhanced fluorescence at 600 nm. Detailed steady-state and time-resolved emission studies revealed that the reassembly phenomenon was highly selective for dsDNA when compared to single-stranded DNA (ssDNA), which allowed us to use the EB-TFP-iCONs as a 2D fluorescent platform for the label-free detection of complementary DNA strands.
Keywords: Covalent organic framework; DNA; ionic assembly; ionic covalent organic nanosheets; label-free detection

Syntheses and single crystal X-ray diffraction analysis of five isostructural 2D MOCCs - Singh, Sandeep K.; Srivastava, Krishna; Banerjee, Rahul; Prasad, Jagdish (Polyhedron, 2018)
Five two-dimensional metal-organic coordination compounds (MOCCs) have been solvothermally synthesized by the combination of 2-aminonicotinic acid (ANA) and transition metal ions, viz. Co(II), Ni (II), Cu(Il), Zn(II) and Cd(II), in water-ethanol mixed solvent. They are formulated as [CoC6H5N2O2)(2)], (Co-ANA); [Ni(C6H5N2O2)(2)], (Ni-ANA) [Cu(C6H5N2O2)(2)], (Cu-ANA), [Zn(C6H5N2O2)(2)], (Zn-ANA) and [Cd(C6H5N2O2)(2)], (Cd-ANA). Single crystal X-ray diffraction studies for the complexes Co-ANA, Ni-ANA and Cd-ANA have also been carried out. These three complexes crystallize in the tetragonal crystal system with the space group P4(1)2(1)2. The metal ions in all these complexes have an octahedral coordination environment. The six coordinations are satisfied by two pyridine N-atoms from two different ANA ligands and four oxygen atoms from two chelating carboxylate groups of another two ANA ligands. The topological motif of the coordination network is defined as 2-periodic net or square lattice (sql). These complexes were further characterized by elemental, FT-IR spectral, thermal and powder X-ray diffraction analyses. (C) 2018 Elsevier Ltd. All rights reserved.

Transforming covalent organic framework into thin-film composite membranes for hydrocarbon recovery - Biswal, Bishnu P. (Separation Science and Technology, 2018)
We, for the first time, employed chemically stable covalent organic framework (COF) (TpPa-1) as a transport-active phase within the polymer (styrene-butadiene rubber; SBR) matrix to make TpPa-1@SBR thin-film composite (TFC) membranes. Three composite membranes, viz., TpPa-1(30)@SBR, TpPa-1(50)@SBR, and TpPa-1(70)@SBR have been prepared with varying COF content. These membranes were characterized for gas permeance and results were compared with the pristine SBR-based TFC membrane. The fully organic nature of chemically stable COF offered good compatibility with the host polymer matrix (SBR) and resulted into flexible TFC membranes even at 70% of COF loading; compared to the other porous material (MOFs or Inorganic fillers), it is appreciable.
Keywords: Covalent organic framework; hydrocarbon recovery; propylene–propane; styrene-butadiene rubber; thin film composite

Ultrastable imine-based covalent organic frameworks for sulfuric acid recovery: an effect of interlayer hydrogen bonding - Halder, Arjun; Karak, Suvendu; Addicoat, Matthew; Bera, Saibal; Chakraborty, Amit; Kunjattu, Shebeeb H.; Pachfule, Pradip; Heine, Thomas; Banerjee, Rahul (Angewandte Chemie-International Edition, 2018)
A rapid and scalable synthesis of six new imine-linked highly porous and crystalline COFs is presented that feature exceptionally high chemical stability in harsh environments including conc. H2SO4 (18M), conc. HCl (12M), and NaOH (9M). This is because of the presence of strong interlayer C-H center dot center dot center dot N hydrogen bonding among the individual layers, which provides significant steric hindrance and a hydrophobic environment around the imine (-C=N-) bonds, thus preventing their hydrolysis in such an abrasive environment. These COFs were further converted into porous, crystalline, self-standing, and crack-free COF membranes (COFMs) with extremely high chemical stability for their potential applications for sulfuric acid recovery. The as-synthesized COFMs exhibit unprecedented permeance for acetonitrile (280 Lm(-2) h(-1) bar(-1)) and acetone (260 Lm(-2) h(-1) bar(-1)).

ZIF-8@DBzPBI-BuI composite membranes for olefin/paraffin separation - Kunjattu, Shebeeb H.; Ashok, Varsha; Bhaskar, Anand; Pandare, Kiran; Banerjee, Rahul; Kharul, Ulhas K. (Journal of Membrane Science, 2018)
ZIF-8 is a member of Zeolitic Imidazole Framework family having high internal surface area, the high thermo-chemical stability and ease of synthesis gained immense attention for its highly selective sieving ability. Transforming it into a membrane form and practical utility remains a challenge. Any success towards this direction would radically reduce the cost of propylene/propane separation. Present study reports use of substituted polybenzimidazole (DBzPBI-BuI) for fabrication of flexible, thus scalable composite membranes with ZIF-8 (ZIF8@DBzPBI-BuI) possessing host-guest compatibility. The membrane with 30% ZIF-8 loading showed promising propylene-propane separation (ideal selectivity of 32.7), coupled with propylene permeability of 12.13 Barrer. Analysis of sorption shed light on the high contribution of diffusivity on governing permeation properties of the composite membranes. The mixed gas analysis offered highly encouraging results in comparison to known composite membranes of different polymers with ZIF-8. Placement of present data on `upper-bound' showed a rapid enhancement in selectivity by the addition of ZIF-8 in the polymer matrix, which seems to be a result of the elimination of inter-phase defects. It was made possible due to the functionality of host polymer.
Keywords: Gas permeation; Olefin/paraffin separation; Polybenzimidazole (PBI); ZIF-8

Covalent organic frameworks: chemistry beyond the structure - Kandambeth, Sharath; Dey, Kaushik; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Covalent organic frameworks (COFs) represent a new field of rapidly growing chemical research that takes direct inspiration from diverse covalent bonds existing between atoms. The success of linking atoms in two and three dimensions to construct extended framework structures moved the chemistry of COFs beyond the structures to methodologies, highlighting the possibility of prospective applications. Although structure to property relation in COFs has led to fascinating properties, chemical stability, processability and scalability were some of the important challenges that needed to be overcome for their successful implementation. In this Perspective, we take a closer look at the growth of COFs from mere supramolecular structures to potential industrializable materials.

Covalent self-assembly in two dimensions: connecting covalent organic framework nanospheres into crystalline and porous thin films - Sasmal, Himadri Sekhar; Halder, Arjun; Kunjattu, Shebeeb; Dey, Kaushik; Nadol, Athulya; Ajithkumar, Thalasseril G.; Bedadur, Prachiti Ravindra; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Insolubility of covalent organic frameworks (COFs) in organic solvents is one of the major obstacles for the potential application of these extended networks such as drug delivery, sensing, optoelectronics, and semiconductor device fabrication. The present work proposes a unique way to make uniform, solution-processable, crystalline, and porous COF nanospheres directly from the homogeneous solution of amine and aldehyde via spatial and temporal control of the nucleation and growth. This strategy of direct nucleation simultaneously showcases the caliber to tune the size of the COF nanospheres from 25 to 570 nm. We have also demonstrated the concept of mesoscale covalent self-assembly of those solution-processable COF nanospheres in the liquid-liquid interface (DCM-water bilayer) for the very first time, transmuting them into self-standing COF thin films with long-range ordered arrangements in two dimensions. The crystalline and porous (with TpAzo showing highest S-BET of 1932 m(2) g(-1)) free-standing COF thin films could be fabricated in a wide range of thicknesses from as low as 21 nm to as high as 630 nm. Both beta-ketoenamine (TpAzo, TpDPP) and imine (TpOMeAzo, TpOMeDPP) linked COF thin films have been synthesized via mesoscale covalent self-assembly of the solution-processable COF nanospheres illustrating the generality of this eloquent methodology. Further, the solution processability has been tested and utilized to cast COF thin films uniformly in the inner and outer surface of an alumina hollow fiber membrane. The COF thin film-alumina hollow fiber membrane composites have showcased promising selective molecular separation of He and O-2, He and CO2, and He and N-2.

Inducing disorder in order: hierarchically porous covalent organic framework nanostructures for rapid removal of persistent organic pollutants - Karak, Suvendu; Dey, Kaushik; Torris, Arun; Halder, Arjun; Bera, Saibal; Kanheerampockil, Fayis; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
The key factor responsible for fast diffusion and mass transfer through a porous material is the availability of a widely open pore interior having complete accessibility from their surface. However, because of their highly stacked nature, ordered two-dimensional (2D) materials fail to find real-world applicability, as it is difficult to take advantage of their complete structure, especially the inner cores. In this regard, three-dimensional (3D) nanostructures constructed from layered two-dimensional crystallites could prove to be advantageous. However, the real challenge is to cultivate a porous nanostructure with ordered pores where the pores are surrounded by crystalline walls. Herein, a simple yet versatile in situ gas-phase foaming technique has been employed to address these cardinal issues. The use of baking soda leads to the continuous effervescence of CO2 during the crystallization of foam, which creates ripples and fluctuations on the surface of the 2D crystallites. The induction of ordered micropores within the disordered 3D architecture synergistically renders fast diffusion of various guests through the interconnected pore network. The high-density defects in the hierarchically porous structure help in ultrafast adsorption (<10 s) of various pollutants (removal efficiency of 99%) from water, all of which would lead to significant environmental benefit. The pseudo-second-order rate constant for the BPA pollutant is 182.3 g mg(-1) min(-1), which is the highest among all the literature reports to date. The high removal efficiency (highest efficiency of 94% and average efficiency of 70%) of a persistent organic pollutant has been attended for the first time.

Porosity switching in polymorphic porous organic cages with exceptional chemical stability - Bera, Saibal; Dey, Kaushik; Pal, Tapan K.; Halder, Arjun; Tothadi, Srinu; Karak, Suvendu; Addicoat, Matthew; Banerjee, Rahul (Angewandte Chemie-International Edition, 2019)
Porous solids that can be switched between different forms with distinct physical properties are appealing candidates for separation, catalysis, and host-guest chemistry. In this regard, porous organic cages (POCs) are of profound interest because of their solution-state accessibility. However, the application of POCs is limited by poor chemical stability. Synthesis of an exceptionally stable imine-linked (4+6) porous organic cage (TpOMe-CDA) is reported using 2,4,6-trimethoxy-1,3,5-triformyl benzene (TpOMe) as a precursor aldehyde. Introduction of the -OMe functional group to the aldehyde creates significant steric and hydrophobic characteristics in the environment around the imine bonds that protects the cage molecules from hydrolysis in the presence of acids or bases. The electronic effect of the -OMe group also plays an important role in enhancing the stability of the reported POCs. As a consequence, TpOMe-CDA reveals exceptional chemical stability in neutral, acidic and basic conditions, even in 12m NaOH. Interestingly, TpOMe-CDA exists in three different porous and non-porous polymorphic forms (, , and ) with respect to differences in crystallographic packing and the orientation of the flexible methoxy groups. All of the polymorphs retain their crystallinity even after treatment with acids and bases. All the polymorphs of TpOMe-CDA differ significantly in their properties as well as morphology and could be reversibly switched in the presence of an external stimulus.
Keywords: chemical stability; Morphology; organic cages; polymorphism; porosity switching

Triazine functionalized porous covalent organic framework for photo-organocatalytic E-Z isomerization of olefins - Bhadra, Mohitosh; Kandambeth, Sharath; Sahoo, Manoj K.; Addicoat, Matthew; Balaraman, Ekambaram; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Visible light-mediated photocatalytic organic transformation has drawn significant attention as an alternative process for replacing thermal reactions. Although precious metal/organic dyes based homogeneous photocatalysts have been developed, their toxic and nonreusable nature makes them inappropriate for large-scale production. Therefore, we have synthesized a triazine and a keto functionalized nonmetal based covalent organic framework (TpTt) for heterogeneous photo catalysis. As the catalyst shows significant absorption of visible light, it has been applied for the photocatalytic uphill conversion of trans-stilbene to cis-stilbene in the presence of blue light-emitting diodes with broad substrate scope via an energy transfer process.

Weak intermolecular interactions in covalent organic framework-carbon nanofiber based crystalline yet flexible devices - Mohammed, Abdul Khayum; Vijayakumar, Vidyanand; Halder, Arjun; Ghosh, Meena; Addicoat, Matthew; Bansode, Umesh; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2019)
<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">The redox-active and porous structural backbone of covalent organic frameworks (COFs) can facilitate high-performance electrochemical energy storage devices. However, the utilities of such 2D materials as supercapacitor electrodes in advanced self-charging power-pack systems have been obstructed due to the poor electrical conductivity and subsequent indigent performance. Herein, we report an effective strategy to enhance the electrical conductivity of COF thin sheets through the in situ solid-state inclusion of carbon nanofibers (CNF) into the COF precursor matrix. The obtained COF-CNF hybrids possess a significant intermolecular π···π interaction between COF and the graphene layers of the CNF. As a result, these COF-CNF hybrids (DqTp-CNF and DqDaTp-CNF) exhibit good electrical conductivity (0.25 × 10<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–3<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> S cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–1<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">), as well as high performance in electrochemical energy storage (DqTp-CNF: 464 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> at 0.25 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">). Also, the fabricated, mechanically strong quasi-solid-state supercapacitor (DqDaTp-CNF SC) delivered an ultrahigh device capacitance of 167 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> at 0.5 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">. Furthermore, we integrated a monolithic photovoltaic self-charging power pack by assembling DqDaTp-CNF SC with a perovskite solar cell. The fabricated self-charging power pack delivered excellent performance in the areal capacitance (42 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">) at 0.25 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> after photocharging for 300 s.

Zinc ion interactions in a two-dimensional covalent organic framework based aqueous zinc ion battery - Mohammed, Abdul Khayum; Ghosh, Meena; Vijayakumar, Vidyanand; Halder, Arjun; Nurhuda, Maryam; Kumar, Sushil; Addicoat, Matthew; Kurungot, Sreekumar; Banerjee, Rahul (Chemical Science, 2019)
<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">The two-dimensional structural features of covalent organic frameworks (COFs) can promote the electrochemical storage of cations like H<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, Li<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, and Na<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> through both faradaic and non-faradaic processes. However, the electrochemical storage of cations like Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ion is still unexplored although it bears a promising divalent charge. Herein, for the first time, we have utilized hydroquinone linked β-ketoenamine COF acting as a Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> anchor in an aqueous rechargeable zinc ion battery. The charge-storage mechanism comprises of an efficient reversible interlayer interaction of Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ions with the functional moieties in the adjacent layers of COF (−182.0 kcal mol<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">). Notably, due to the well-defined nanopores and structural organization, a constructed full cell, displays a discharge capacity as high as 276 mA h g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> at a current rate of 125 mA g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">.

Connecting microscopic structures, mesoscale assemblies, and macroscopic architectures in 3D-printed hierarchical porous covalent organic framework foams - Mohammed, Abdul Khayum; Usgaonkar, Saurabh; Kanheerampockil, Fayis; Karak, Suvendu; Halder, Arjun; Tharkar, Minakshi; Addicoat, Matthew; Ajithkumar, Thalasseril G.; Banerjee, Rahul (Journal of the American Chemical Society, 2020)
The induction of macro and mesopores into two-dimensional porous covalent organic frameworks (COFs) could enhance the exposure of the intrinsic micropores toward the pollutant environment, thereby, improving the performance. However, the challenge is to build a continuous hierarchically porous macro-architecture of crystalline organic materials in the bulk scale. In this regard, we have strategized a novel synthetic method to create hierarchically porous COF foams consisting of ordered micropores (2-2.2 nm) and disordered meso and macropores (50 nm to 200 mu m) as well as ordered macropores (1.5 mm to 2 cm). Herein, graphene oxide was used for creating disordered macro and mesopores in COF-GO foams. Considering the rheological features of the precursor hydrogel, we could integrate crystalline and porous COF-GO foams into self-supported three-dimensional (3D)-printed objects with the desired shapes and sizes. Therefore, we have engineered the 3D macro-architecture of COF-GO foams into complex geometries keeping their structural order and continuous porosity intact over a range of more than a million (10(-9) m to 10(-3) m). The interconnected 3D openings in these COF-GO foams further enhance the rapid and efficient uptake of organic and inorganic pollutants from water (>95% removal within 30 s). The abundant distribution of interconnected macroporous volume (55%) throughout the COF-GO foam matrix enhances the flow of water (1.13 x 10(-3) m.s(-1)) which results in efficient mass transport and adsorption.

Morphological evolution of two-dimensional porous hexagonal trimesic acid framework - Tothadi, Srinu; Koner, Kalipada; Dey, Kaushik; Addicoat, Matthew; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2020)
Hexagonal single crystal structure (Form II) of trimesic acid (TMA) has been isolated by dissolving the interpenetrated Form I of TMA in tetrahydrofuran. Form II (hexagonal) was converted to Form I (interpenetrated) at room temperature through some intermediate structures. A detailed time-dependent FESEM study shows that the external morphology of Form II (hexagonal) is a hollow hexagonal tube that mimics its crystal structure. The block-shaped (morphology) of Form I (interpenetrated) was converted to the hollow hexagonal tube through some intermediate morphologies which are corresponding to particular crystal structures. Here, we have established a strong correlation between crystal structures with the morphology. These hollow tubes have been employed for Rhodamine B dye adsorption studies and showed an uptake of 82%, much more significant than Form I (interpenetrated) (39%) due to the presence of a pore channel in the crystal structure.
Keywords: dye adsorption; hollow hexagonal rod; hydrogen-bonded organic framework; morphology evaluation; trimesic acid

Nanoparticle size-fractionation through self-standing porous covalent organic framework films - Dey, Kaushik; Kunjattu, Shebeeb H.; Chahande, Anurag M.; Banerjee, Rahul (Angewandte Chemie-International Edition, 2020)
Covalent organic frameworks (COFs) have attracted attention due to their ordered pores leading to important industrial applications like storage and separation. Combined with their modular synthesis and pore engineering, COFs could become ideal candidates for nanoseparations. However, the fabrication of these microcrystalline powders as continuous, crack-free, robust films remains a challenge. Herein, we report a simple, slow annealing strategy to construct centimeter-scale COF films (Tp-Azo and Tp-TTA) with micrometer thickness. The as-synthesized films are porous (SA(BET)=2033 m(2) g(-1) for Tp-Azo) and chemically stable. These COFs have distinct size cut-offs (ca. 2.7 and ca. 1.6 nm for Tp-Azo and Tp-TTA, respectively), which allow the size-selective separation of gold nanoparticles. Unlike, other conventional membranes, the durable structure of the COF films allow for excellent recyclability (up to 4 consecutive cycles) and easy recovery of the gold nanoparticles from the solution.
Keywords: covalent organic frameworks; films; nanofilter; Nanoparticles; size-selective separation

Triazine-based organic polymer-catalysed conversion of epoxide to cyclic carbonate under ambient CO2 pressure - Biswas, Tanmoy; Halder, Arjun; Paliwal, Khusboo S.; Mitra, Antarip; Tudu, Gouri; Banerjee, Rahul; Mahalingam, Venkataramanan (Chemistry-An Asian Journal, 2020)
In this work we have achieved epoxide to cyclic carbonate conversion using a metal-free polymeric catalyst under ambient CO2 pressure (1.02 atm) using a balloon setup. The triazine containing polymer (CYA-ANIS) was prepared from cyanuric chloride (CYA-Cl) and o-dianisidine (ANIS) in anhydrous DMF as solvent by refluxing under the N-2 gas environment. The presence of triazine and amine functional groups in the polymer results in the adsorption of CO2 up to 7 cc/g at 273 K. This inspired us to utilize the polymer for the conversion of a series of functionalised epoxides into their corresponding cyclic carbonates in the presence of tetrabutyl ammonium iodide (TBAI) as co-catalyst. The product has wide range of applications like solvent in lithium ion battery, precursor for polycarbonate, etc. The catalyst was efficient for the conversion of different mono and di-epoxides into their corresponding cyclic carbonates under atmospheric pressure in the presence of TBAI as co-catalyst. The study indicates that epoxide attached with electron withdrawing groups (like, CH2Cl, glycidyl ether, etc.) displayed better conversion compared to simple alkane chain attached epoxides. This is mainly due to the stabilization of electron rich intermediates produced during the reaction (e. g. epoxide ring opening or CO2 incorporation into the halo-alkoxide anion). This catalyst mixture was capable to maintain its reactivity up to five cycles without losing its activity. Post catalytic characterization clearly supports the heterogeneous and recyclable nature of the catalyst.
Keywords: CO2 fixation; cyclic carbonates; epoxides; Heterogeneouscatalyst; metal free catalyst; Triazinepolymer

Heterogeneous C-H functionalization in water via porous covalent organic framework nanofilms: a case of catalytic sphere transmutation - Sasmal, Himadri Sekhar; Bag, Saikat; Chandra, Bittu; Majumder, Poulami; Kuiry, Himangshu; Karak, Suvendu; Sen Gupta, Sayam; Banerjee, Rahul (Journal of the American Chemical Society, 2021)
Heterogeneous catalysis in water has not been explored beyond certain advantages such as recyclability and recovery of the catalysts from the reaction medium. Moreover, poor yield, extremely low selectivity, and active catalytic site deactivation further underrate the heterogeneous catalysis in water. Considering these facts, we have designed and synthesized solution-dispersible porous covalent organic framework (COF) nanospheres. We have used their distinctive morphology and dispersibility to functionalize unactivated C-H bonds of alkanes heterogeneously with high catalytic yield (42-99%) and enhanced regioand stereoselectivity (3 degrees:2 degrees = 105:1 for adamantane). Further, the fabrication of catalyst-immobilized COF nanofilms via covalent self-assembly of catalytic COF nanospheres for the first time has become the key toward converting the catalytically inactive homogeneous catalysts into active and effective heterogeneous catalysts operating in water. This unique covalent self-assembly occurs through the protrusion of the fibers at the interface of two nanospheres, transmuting the catalytic spheres into films without any leaching of catalyst molecules. The catalyst-immobilized porous COF nanofilms' chemical functionality and hydrophobic environment stabilize the high-valent transient active oxoiron(V) intermediate in water and restricts the active catalytic site's deactivation. These COF nanofilms functionalize the unactivated C-H bonds in water with a high catalytic yield (45-99%) and with a high degree of selectivity (cis:trans = 155:1; 3 degrees:2 degrees = 257:1, for cis-1,2-dimethylcyclohexane). To establish this approach's ``practical implementation'', we conducted the catalysis inflow (TON = 424 +/- 5) using catalyst-immobilized COF nanofilms fabricated on a macroporous polymeric support.

Dual nanomechanics in anisotropic porous covalent organic framework janus-type thin films - Mohata, Shibani; Dey, Kaushik; Bhunia, Surojit; Thomas, Neethu; Gowd, E. Bhoje; Ajithkumar, Thalasseril G.; Reddy, C. Malla; Banerjee, Rahul (Journal of the American Chemical Society, 2022)
Empowered by crystalline ordered structures and homogeneous fabrication techniques, covalent organic frameworks (COFs) have been realized with uniform morphologies and isotropic properties. However, such homogeneity often hinders various surface-dependent properties observed in asymmetric nanostructures. The challenge remains to induce heterogeneity in COFs by creating an asymmetric superstructure such as a Janus thin film. In this regard, we propose a versatile yet straightforward interfacial layer-grafting strategy to fabricate free-standing Janus-type COF-graphene thin films. Herein, two-dimensional graphene sheets were utilized as the suitable grafter due to the possibility of noncovalent interactions between the layers. The versatility of the approach was demonstrated by fabricating two distinct Janus-type films, with the COF surface interwoven with nanofibers and nanospheres. The Janus-type films showcase opposing surface morphologies originating from graphene sheets and COF nanofibers or nanospheres, preserving the porosity (552-600 m(2) g(-1)). The unique surface chemistries of the constituent layers further endow the films with orthogonal mechanical properties, as confirmed by the nanoindentation technique. Interestingly, the graphene sheets favor the Janus-type assembly of COF nanofibers over the nanospheres. This is reflected in the better nanomechanical properties of COFfiber-graphene films (E-gra(phene) = 300-1200 MPa; E-COF( )= 15-60 MPa) compared to the COFsphere-graphene films (E-gra(phe)ne = 11-14 MPa; E-CO(F )= 2-5 MPa). These results indicate a direct relationship between the mechanical properties and homo/heterogeneity of Janus-type COF films.

Porous covalent organic nanotubes and their assembly in loops and toroids - Koner, Kalipada; Karak, Shayan; Kandambeth, Sharath; Karak, Suvendu; Thomas, Neethu; Leanza, Luigi; Perego, Claudio; Pesce, Luca; Capelli, Riccardo; Moun, Monika; Bhakar, Monika; Ajithkumar, Thalasseril G.; et al. (Nature Chemistry, 2022)
Carbon nanotubes, and synthetic organic nanotubes more generally, have in recent decades been widely explored for application in electronic devices, energy storage, catalysis and biosensors. Despite noteworthy progress made in the synthesis of nanotubular architectures with well-defined lengths and diameters, purely covalently bonded organic nanotubes have remained somewhat challenging to prepare. Here we report the synthesis of covalently bonded porous organic nanotubes (CONTs) by Schiff base reaction between a tetratopic amine-functionalized triptycene and a linear dialdehyde. The spatial orientation of the functional groups promotes the growth of the framework in one dimension, and the strong covalent bonds between carbon, nitrogen and oxygen impart the resulting CONTs with high thermal and chemical stability. Upon ultrasonication, the CONTs form intertwined structures that go on to coil and form toroidal superstructures. Computational studies give some insight into the effect of the solvent in this assembly process.

Viscoelastic covalent organic nanotube fabric via macroscopic entanglement - Koner, Kalipada; Das, Susobhan; Mohata, Shibani; Duong, Nghia Tuan; Nishiyama, Yusuke; Kandambeth, Sharath; Karak, Suvendu; Reddy, C. Malla; Banerjee, Rahul (Journal of the American Chemical Society, 2022)
Covalent organic nanotubes (CONTs) are one-dimensional porous frameworks constructed from organic building blocks via dynamic covalent chemistry. CONTs are synthesized as insoluble powder that restricts their potential applications. The judicious selection of 2,2'-bipyridine-5,5'-dicarbaldehyde and tetraaminotriptycene as building blocks for TAT-BPy CONTs has led to constructing flexible yet robust and self-standing fabric up to 3 mu m thickness. The TAT-BPy CONTs and TAT-BPy CONT fabric have been characterized by solid-state one-dimensional (1D) C-13 CP-MAS, two-dimensional (2D) C-13-H-1 correlation NMR, 2D H-1-H-1 DQ-SQ NMR, and 2D N-14-H-1 correlation NMR spectroscopy. The mechanism of fabric formation has been established by using high-resolution transmission electron microscopy and scanning electron microscopy techniques. The as-synthesized viscoelastic TAT-BPy CONT fabric exhibits high mechanical strength with a reduced modulus (E-r) of 8 (+/- 3) GPa and hardness (H) of 0.6 (+/- 0.3) GPa. Interestingly, the viscoelastic fabric shows time-dependent elastic depth recovery up to 50-70%.

Covalent organic framework cladding on peptide-amphiphile-based biomimetic catalysts - Kumar Mahato, Ashok; Pal, Sumit; Dey, Kaushik; Reja, Antara; Paul, Satyadip; Shelke, Ankita; Ajithkumar, Thalasseril G.; Das, Dibyendu; Banerjee, Rahul (Journal of the American Chemical Society, 2023)
Peptide-based biomimetic catalysts are promising materialsforefficient catalytic activity in various biochemical transformations.However, their lack of operational stability and fragile nature innon-aqueous media limit their practical applications. In this study,we have developed a cladding technique to stabilize biomimetic catalystswithin porous covalent organic framework (COF) scaffolds. This methodologyallows for the homogeneous distribution of peptide nanotubes insidethe COF (TpAzo and TpDPP) backbone, creating strong noncovalent interactionsthat prevent leaching. We synthesized two different peptide-amphiphiles,C10FFVK and C10FFVR, with lysine (K) and arginine(R) at the C-termini, respectively, which formed nanotubular morphologies.The C10FFVK peptide-amphiphile nanotubes exhibit enzyme-likebehavior and efficiently catalyze C-C bond cleavage in a buffermedium (pH 7.5). We produced nanotubular structures of TpAzo-C10FFVK and TpDPP-C10FFVK through COF claddingby using interfacial crystallization (IC). The peptide nanotubes encasedin the COF catalyze C-C bond cleavage in a buffer medium aswell as in different organic solvents (such as acetonitrile, acetone,and dichloromethane). The TpAzo-C10FFVK catalyst,being heterogeneous, is easily recoverable, enabling the reactionto be performed for multiple cycles. Additionally, the synthesis ofTpAzo-C10FFVK thin films facilitates catalysis inflow. As control, we synthesized another peptide-amphiphile, C10FFVR, which also forms tubular assemblies. By depositingTpAzo COF crystallites on C10FFVR nanotubes through IC,we produced TpAzo-C10FFVR nanotubular structuresthat expectedly did not show catalysis, suggesting the critical roleof the lysines in the TpAzo-C10FFVK.

Covalent organic framework thin-film photodetectors from solution-processable porous nanospheres - Bag, Saikat; Sasmal, Himadri Sekhar; Chaudhary, Sonu Pratap; Dey, Kaushik; Blaette, Dominic; Guntermann, Roman; Zhang, Yingying; Poloz, Miroslav; Kuc, Agnieszka; Shelke, Ankita; Vijayaraghavan, Ratheesh K.; Ajithkumar, Thalasseril G.; et al. (Journal of the American Chemical Society, 2023)
The synthesis of homogeneous covalent organic framework (COF) thin films on a desired substrate with decent crystallinity, porosity, and uniform thickness has great potential for optoelectronic applications. We have used a solution-processable sphere transmutation process to synthesize 300 +/- 20 nm uniform COF thin films on a 2 x 2 cm2 TiO2-coated fluorine-doped tin oxide (FTO) surface. This process controls the nucleation of COF crystallites and molecular morphology that helps the nanospheres to arrange periodically to form homogeneous COF thin films. We have synthesized four COF thin films (TpDPP, TpEtBt, TpTab, and TpTta) with different functional backbones. In a close agreement between the experiment and density functional theory, the TpEtBr COF film showed the lowest optical band gap (2.26 eV) and highest excited-state lifetime (8.52 ns) among all four COF films. Hence, the TpEtBr COF film can participate in efficient charge generation and separation. We constructed optoelectronic devices having a glass/FTO/TiO2/COF-film/Au architecture, which serves as a model system to study the optoelectronic charge transport properties of COF thin films under dark and illuminated conditions. Visible light with a calibrated intensity of 100 mW cm-2 was used for the excitation of COF thin films. All of the COF thin films exhibit significant photocurrent after illumination with visible light in comparison to the dark. Hence, all of the COF films behave as good photoactive substrates with minimal pinhole defects. The fabricated out-of-plane photodetector device based on the TpEtBr COF thin film exhibits high photocurrent density (2.65 +/- 0.24 mA cm-2 at 0.5 V) and hole mobility (8.15 +/- 0.64 x10-3 cm2 V-1 S-1) compared to other as synthesized films, indicating the best photoactive characteristics.

Hierarchical covalent organic framework-foam for multi-enzyme tandem catalysis - Paul, Satyadip; Gupta, Mani; Dey, Kaushik; Mahato, Ashok Kumar; Bag, Saikat; Torris, Arun; Gowd, E. Bhoje; Sajid, Hasnain; Addicoat, Matthew A.; Datta, Supratim; Banerjee, Rahul (Chemical Science, 2023)
Covalent organic frameworks (COFs) are ideal host matrices for biomolecule immobilization and biocatalysis due to their high porosity, various functionalities, and structural robustness. However, the porosity of COFs is limited to the micropore dimension, which restricts the immobilization of enzymes with large volumes and obstructs substrate flow during enzyme catalysis. A hierarchical 3D nanostructure possessing micro-, meso-, and macroporosity could be a beneficial host matrix for such enzyme catalysis. In this study, we employed an in situ CO2 gas effervescence technique to induce disordered macropores in the ordered 2D COF nanostructure, synthesizing hierarchical TpAzo COF-foam. The resulting TpAzo foam matrix facilitates the immobilization of multiple enzymes with higher immobilization efficiency (approximately 1.5 to 4-fold) than the COF. The immobilized cellulolytic enzymes, namely beta-glucosidase (BGL), cellobiohydrolase (CBH), and endoglucanase (EG), remain active inside the TpAzo foam. The immobilized BGL exhibited activity in organic solvents and stability at room temperature (25 degrees C). The enzyme-immobilized TpAzo foam exhibited significant activity towards the hydrolysis of p-nitrophenyl-beta-d-glucopyranoside (BGL@TpAzo-foam: K-m and V-max = 23.5 +/- 3.5 mM and 497.7 +/- 28.0 mu M min(-1)) and carboxymethylcellulose (CBH@TpAzo-foam: K-m and V-max = 18.3 +/- 4.0 mg mL(-1) and 85.2 +/- 9.6 mu M min(-1) and EG@TpAzo-foam: K-m and V-max = 13.2 +/- 2.0 mg mL(-1) and 102.2 +/- 7.1 mu M min(-1)). Subsequently, the multi-enzyme immobilized TpAzo foams were utilized to perform a one-pot tandem conversion from carboxymethylcellulose (CMC) to glucose with high recyclability (10 cycles). This work opens up the possibility of synthesizing enzymes immobilized in TpAzo foam for tandem catalysis.

Morphology tuning via linker modulation: metal-free covalent organic nanostructures with exceptional chemical stability for electrocatalytic water splitting - Karak, Shayan; Koner, Kalipada; Karmakar, Arun; Mohata, Shibani; Nishiyama, Yusuke; Duong, Nghia Tuan; Thomas, Neethu; Ajithkumar, Thalasseril Govindankuttykaimal; Hossain, Munshi Sahid; Bandyopadhyay, Subhajit; Kundu, Subrata; Banerjee, Rahul (Advanced Materials, 2024)
The development of synthetic routes for the formation of robust porous organic polymers (POPs) with well-defined nanoscale morphology is fundamentally significant for their practical applications. The thermodynamic characteristics that arise from reversible covalent bonding impart intrinsic chemical instability in the polymers, thereby impeding their overall potential. Herein, a unique strategy is reported to overcome the stability issue by designing robust imidazole-linked POPs via tandem reversible/irreversible bond formation. Incorporating inherent rigidity into the secondary building units leads to robust microporous polymeric nanostructures with hollow-spherical morphologies. An in-depth analysis by extensive solid-state NMR (1D and 2D) study on H-1, C-13, and N-14 nuclei elucidates the bonding and reveals the high purity of the newly designed imidazole-based POPs. The nitrogen-rich polymeric nanostructures are further used as metal-free electrocatalysts for water splitting. In particular, the rigid POPs show excellent catalytic activity toward the oxygen evolution reaction (OER) with long-term durability. Among them, the most efficient OER electrocatalyst (TAT-TFBE) requires 314 mV of overpotential to drive 10 mA cm(-2) current density, demonstrating its superiority over state-of-the-art catalysts (RuO2 and IrO2).
Keywords: bi-functional electrocatalysts; chemically robust; hollow-spherical morphologies; imidazole-linked; inherent rigidity; metal-free; water splitting

Chirality transfer from covalent organic framework nanotubes to covalent organic framework films via chirality induction crystallization - Bag, Saikat; Chatterjee, Debasmita; Mahapatra, Rohan; Sasmal, Himadri Sekhar; Khatua, Arindam; Giri, Madhurima; Paul, Satyadip; Shelke, Ankita; Almasoud, Najla; Alomar, Taghrid S.; Ajithkumar, Thalasseril G.; Sen Gupta, Sayam; et al. (Advanced Materials, 2026)
We report the synthesis of homochiral crystalline covalent organic framework (COF) films that combine rigidity and porosity, offering significant promise for heterogeneous asymmetric catalysis. We prepared enantiopure COF films from achiral diamine and trialdehyde precursors using a chiral induction crystallization strategy. A Schiff-base reaction, catalyzed by a chiral acid, namely (R)- and (S)-camphorsulfonic acids (CSA) generated a beta-ketoenamine backbone with induced chirality. (R)- and (S)-camphorsulfonic acids direct the diamine-trialdehyde condensation and induce chirality during the nucleation of COF nanotubes, enabling their periodic arrangement and the formation of homochiral thin films. We successfully synthesized six distinct COF films with three different backbone functionalities: R-, S-TpAzo; R-, S-TpDPP; and R-, S-TpBDMe2, using the two enantiomers of the chiral camphorsulfonic acids. All films displayed strong circular dichroism signals and pronounced Cotton effects, confirming their enhanced enantiopurity. Both R- and S-TpAzo films exhibited the highest crystallinity, long-range order, and permanent porosity, making them particularly well-suited for catalytic applications. To demonstrate their utility, we encapsulated a bioinspired catalyst, (Et4N)2[FeIII(Cl)bTAML], within the chiral channels of the R- and S-TpAzo films. The resulting composite created a robust heterogeneous catalytic platform for the asymmetric epoxidation of alkenes, achieving excellent activity and enantioselectivity under ambient conditions.
Keywords: chiral induction; covalent organic framework nanotube; covalent organic framework thin film; heterogeneous catalysis